Optical adhesive sheet

By using optical pressure-sensitive films with low shear storage modulus, the film can be photocured under light and exhibits high elongation and stress-relaxation capabilities, solving the problem that existing films are difficult to track pace and stress concentration during bonding, achieving efficient bubble reduction and adhesion stability.

JP2025051618APending Publication Date: 2025-04-04NITTO DENKO CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2024153815
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-09-22
Filing Date
2024-09-06
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

In the bonding process, existing optical pressure-sensitive films are difficult to track the surface step, resulting in bubble formation, and high-elastic films are prone to concentrate stress on the contact surface, resulting in unstable adhesion.

Method used

An optical pressure sensitive film with low shear storage modulus was used, which had a shear storage modulus of 0.3 MPa or less at 25°C and contained a matrix polymer that was photocurable under light and exhibited high elongation and stress-relaxation capabilities in tensile tests.

Benefits of technology

It realizes good step tracking ability during bonding, reduces bubble formation, improves the stability and reliability of the paste, and maintains high elasticity to prevent stress concentration on the adhesion surface.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025051618000001_ABST
    Figure 2025051618000001_ABST
Patent Text Reader

Abstract

To provide an optical adhesive sheet which realizes favorable step followability when bonding between adherends, and is suitable for attaining both bubble inhibition and joint reliability after bonding between adherends.SOLUTION: An adhesive sheet 10 is an optical adhesive sheet including a base polymer, and having photo-curability. The base polymer is a photopolymerized product of polymerizable constituents including a monofunctional monomer, and a photopolymerizable polyfunctional compound. The adhesive sheet 10 has a shear storage elastic modulus G1 of 0.3 MPa or lower at 25°C. The adhesive sheet 10 satisfies Bs≥-0.17G2+3.74 after curing by ultraviolet irradiation under a condition of an integrated irradiation light amount of 3000 mJ / cm2 with regard to a rupture strain Bs by a tensile test under a condition of 23°C and 300 mm / min. of a tension rate, and a shear storage elastic modulus G2 at 25°C.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an optical pressure-sensitive adhesive sheet. [Background technology]

[0002] A display panel has a laminated structure including elements such as a pixel panel, a polarizing film, and a cover glass. In the manufacturing process of a display panel, for example, an optically transparent adhesive sheet (optical adhesive sheet) is used to bond the elements included in the laminated structure. An optical adhesive sheet for use in a display panel is described in, for example, Patent Document 1 below. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2010-97070 A Summary of the Invention [Problem to be solved by the invention]

[0004] The laminated structure of the display panel includes an element having a surface step. For example, a decorative or light-shielding printed layer is provided on the edge of the pixel panel side surface of the cover glass. The printed layer is provided, for example, around the entire edge of the cover glass. This printed layer has a predetermined thickness. Therefore, on the pixel panel side of the cover glass, there is a step (printed step) between the cover glass surface and the printed layer surface. Therefore, the optical adhesive sheet for display panel use is required to be soft enough to follow the printed step (step followability). Insufficient step followability of the optical adhesive sheet is undesirable, for example, because it causes air bubbles to be formed along the printed layer between the optical adhesive sheet attached to the printed layer surface of the cover glass and the cover glass.

[0005] From the viewpoint of conformity to unevenness, it is preferable that the optical adhesive sheet is soft. However, the softer the conventional optical adhesive sheet, the lower the cohesiveness, and therefore air bubbles are likely to be generated at the interface between the adherend and the optical adhesive sheet to which the optical adhesive sheet is attached (air bubbles are formed, for example, with foreign matter as a nucleus).

[0006] Therefore, from the viewpoint of suppressing air bubbles, high elasticity is required for the optical adhesive sheet (i.e., the adhesive that forms the optical adhesive sheet). However, in a conventional optical adhesive sheet, the higher the elasticity, the more likely stress is to be concentrated at the interface with the adherend to which the optical adhesive sheet is bonded. In a state in which such stress is concentrated on the optical adhesive sheet, the optical adhesive sheet is likely to peel off from the adherend, which is undesirable (reduced bonding reliability). For example, in the manufacturing process of a display panel, a state in which the above-mentioned stress is concentrated on the adhesive sheet after two members are bonded together with the optical adhesive sheet may be undesirable because physical stimulation to the end of the adhesive sheet may trigger peeling between the members.

[0007] The optical adhesive sheet is required to have a pressure-sensitive adhesive design that has good step-following ability when bonding between adherends, as well as high elasticity for suppressing bubbles at the interface with the adherend and stress relaxation for suppressing peeling at the interface. The present inventors have considered the optical adhesive sheet in this way and arrived at the present invention.

[0008] The present invention provides an optical adhesive sheet that realizes good conformability to unevenness when bonding adherends together, and is suitable for simultaneously suppressing air bubbles and ensuring bonding reliability after bonding between adherends. [Means for solving the problem]

[0009] The present invention [1] is an optical adhesive sheet that contains a base polymer and has photocurability, the base polymer being a photopolymerization product of a polymerizable component that contains a monofunctional monomer and a photopolymerizable polyfunctional compound, and has a shear storage modulus G1 of 0.3 MPa or less at 25°C and an accumulated light dose of 3000 mJ / cm. 2The optical adhesive sheet includes an optical adhesive sheet in which, after curing by ultraviolet irradiation under the above conditions, the breaking strain Bs in a tensile test under conditions of 23°C and a tensile speed of 300 mm / min and the shear storage modulus G2 at 25°C satisfy Bs ≧ -0.17G2 + 3.74.

[0010] The present invention [2] includes the optical adhesive sheet described in the above [1], in which the ratio of the shear storage modulus G2 to the shear storage modulus G1 is 300 or less.

[0011] The present invention [3] includes the optical adhesive sheet according to the above [1] or [2], in which the breaking strain Bs is 2.0 or more.

[0012] The present invention [4] includes an optical adhesive sheet according to any one of [1] to [3] above, which has an adhesive strength F of 2.0 N / 10 mm or more in the following peel test.

[0013] Peel test: First, a 100 mm long x 10 mm wide adhesive sheet piece of the optical adhesive sheet is attached to an alkali glass plate prepared by the float method to obtain a laminate. Next, the laminate is heated and pressurized at 50°C, 0.5 MPa, and 15 minutes. Next, the adhesive sheet piece in the laminate is irradiated with an integrated light dose of 3000 mJ / cm from the alkali glass plate side. 2 The adhesive sheet piece is then irradiated with ultraviolet light under the conditions of 23° C., a peeling angle of 180°, and a pulling speed of 300 mm / min to pull one end of the adhesive sheet piece in the longitudinal direction, thereby peeling the adhesive sheet piece from the alkali glass plate and measuring the adhesive strength F. Effect of the Invention

[0014] As described above, the optical adhesive sheet of the present invention has a shear storage modulus G1 of 0.3 MPa or less at 25°C and is photocurable. Such an optical adhesive sheet can be attached to a stepped surface of an adherend in a soft state before being cured (photocured) by light irradiation (can be photocured after attachment). Therefore, the optical adhesive sheet is suitable for achieving good step conformability when attached to an adherend having a stepped surface.

[0015] In addition, in the optical adhesive sheet of the present invention, as described above, the base polymer is a photopolymerization product of a polymerizable component containing a monofunctional monomer and a photopolymerizable polyfunctional compound. Such a base polymer has a network structure in which linear units derived from a monofunctional monomer are linked by a photopolymerizable polyfunctional compound. When the optical adhesive sheet is irradiated with light, the optical adhesive sheet containing the base polymer having such a network structure is photocured. This is suitable for ensuring high elasticity in the optical adhesive sheet after photocuring.

[0016] In addition, as described above, the optical adhesive sheet of the present invention, after photocuring under a predetermined condition, has a breaking strain Bs in a tensile test under conditions of 23 ° C and a tensile speed of 300 mm / min and a shear storage modulus G2 at 25 ° C satisfying Bs ≧ -0.17G2 + 3.74. This is suitable for achieving both high elasticity and stress relaxation in the optical adhesive sheet after photocuring. And, achieving both high elasticity and stress relaxation in the optical adhesive sheet after photocuring that bonds between adherends is useful for achieving both the above-mentioned bubble suppression and bonding reliability.

[0017] Therefore, the optical pressure-sensitive adhesive sheet of the present invention realizes good conformability to unevenness when bonding adherends together, and is suitable for simultaneously suppressing air bubbles and ensuring bonding reliability after bonding between adherends. [Brief description of the drawings]

[0018] [Figure 1] 1 is a schematic cross-sectional view of one embodiment of an optical adhesive sheet of the present invention. [Diagram 2]This shows an example of a method for producing an optical adhesive sheet shown in Fig. 1. Fig. 2A shows a step of forming a coating film of an adhesive composition, Fig. 2B shows a step of forming a base adhesive sheet, Fig. 2C shows a step of peeling one of the release liners, Fig. 2D shows a step of supplying a post-added component to the base adhesive sheet, and Fig. 2E shows a step of bonding the release liner to the adhesive sheet. [Diagram 3] This shows an example of a method of using the optical adhesive sheet shown in Fig. 1. Fig. 3A shows a process of attaching the optical adhesive sheet to a member (adherend), Fig. 3B shows a process of joining members together via the optical adhesive sheet, and Fig. 3C shows a process of photocuring the optical adhesive sheet between the members. [Figure 4] 1 is a graph plotting the measurement results of the shear storage modulus G2 and breaking strain Bs of each pressure-sensitive adhesive sheet of the examples and comparative examples. [Diagram 5] 1 shows the positional relationship between the glass plate and the pressure-sensitive adhesive sheet in the laminate used to evaluate the step-conforming ability for the Examples and Comparative Examples. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0019] As shown in Fig. 1, an adhesive sheet 10 according to one embodiment of the present invention has a sheet shape of a predetermined thickness and extends in a direction (plane direction) perpendicular to a thickness direction H. The adhesive sheet 10 has an adhesive surface 11 (first adhesive surface) and an adhesive surface 12 (second adhesive surface) opposite to the adhesive surface 11. Fig. 1 exemplarily shows a state in which release liners 21, 22 are attached to the adhesive surfaces 11, 12 of the adhesive sheet 10. The release liner 21 is in releasable contact with the adhesive surface 11. The release liner 22 is in releasable contact with the adhesive surface 12.

[0020] The adhesive sheet 10 is an optically transparent adhesive sheet (optical adhesive sheet). The adhesive sheet 10 contains a base polymer and has photocurability. In this embodiment, the adhesive sheet 10 further contains a multifunctional monomer and a photopolymerization initiator and has photocurability. Such an adhesive sheet 10 is, for example, an optical adhesive sheet arranged at a light passing portion in a display panel. Examples of the display panel include a liquid crystal display panel and an organic EL display panel. The display panel has a laminated structure including elements such as a pixel panel, a polarizing film, a touch panel, and a cover glass. The adhesive sheet 10 is used, for example, in the manufacturing process of the display panel to bond elements included in the laminated structure.

[0021] The base polymer is a photopolymerization product of a polymerizable component containing a monofunctional monomer and a photopolymerizable polyfunctional compound. Photopolymerization is a polymerization method in which a polymerization reaction of a polymerizable component is advanced by irradiation with active energy rays such as ultraviolet rays. A photopolymerization product is a product formed by such a polymerization method. Such a base polymer has a network structure in which linear units derived from a monofunctional monomer are linked by a photopolymerizable polyfunctional compound as a crosslinking agent.

[0022] The pressure-sensitive adhesive sheet 10 has a shear storage modulus G1 (modulus of elasticity before curing) of 0.3 MPa or less at 25° C. The method for measuring the shear storage modulus G1 is as described below in the Examples. 2After curing by ultraviolet irradiation under the above conditions, the breaking strain Bs in a tensile test under conditions of 23°C and a tensile speed of 300 mm / min and the shear storage modulus G2 (modulus after curing) at 25°C satisfy Bs≧-0.17G2+3.74. The breaking strain Bs is the ratio (ΔL / L0) of the extension length ΔL of the test piece at the time when the test piece breaks to the initial length L0 of the test piece of the pressure-sensitive adhesive sheet 10 in the tensile test. The extension length ΔL is the amount of extension from the initial length L0 of the test piece. The method for measuring the breaking strain Bs is specifically as described later in the examples. The thickness of the pressure-sensitive adhesive sheet 10 in measuring the breaking strain Bs of the pressure-sensitive adhesive sheet 10 is 420 μm±80 μm. If the thickness of the pressure-sensitive adhesive sheet 10 is within the above range, the same evaluation can be obtained. Alternatively, a plurality of pressure-sensitive adhesive sheets 10 may be separately manufactured and then laminated to set the thickness of the pressure-sensitive adhesive sheet 10 within the above range. The method for measuring the shear storage modulus G2 is as described below in relation to the Examples.

[0023] As described above, the adhesive sheet 10 has a shear storage modulus G1 of 0.3 MPa or less at 25°C, and is photocurable. Such an adhesive sheet 10 can be attached to a stepped surface of an adherend in a soft state before being cured by light irradiation (photocuring) (photocuring can be performed after attachment). Therefore, the adhesive sheet 10 is suitable for achieving good step conformability when attached to an adherend having a stepped surface.

[0024] In addition, in the adhesive sheet 10, as described above, the base polymer is a photopolymer of a polymerizable component containing a monofunctional monomer and a photopolymerizable multifunctional compound. Such a base polymer has a network structure as described above. When the adhesive sheet 10 is irradiated with light, the adhesive sheet 10 containing the base polymer with such a network structure is photocured. This is suitable for ensuring high elasticity in the adhesive sheet 10 after photocuring.

[0025] Furthermore, as described above, after photocuring under predetermined conditions, the adhesive sheet 10 has a breaking strain Bs in a tensile test at 23°C and a tensile speed of 300 mm / min and a shear storage modulus G2 at 25°C that satisfy Bs≧−0.17G2+3.74. This is suitable for achieving both high elasticity and stress relaxation properties in the photocured adhesive sheet 10. The compatibility of high elasticity and stress relaxation properties in the photocured adhesive sheet 10 that bonds adherends helps to achieve both the above-mentioned bubble suppression and bonding reliability.

[0026] Therefore, the pressure-sensitive adhesive sheet 10 realizes good conformability to unevenness when bonding adherends together, and is suitable for simultaneously suppressing air bubbles and ensuring bonding reliability after bonding of the adherends together.

[0027] From the viewpoint of the step-following property of the adhesive sheet 10 before photocuring, the shear storage modulus G1 is preferably 0.25 MPa or less, more preferably 0.2 MPa or less, more preferably 0.18 MPa or less, more preferably 0.16 MPa or less, more preferably 0.15 MPa or less, more preferably 0.14 MPa or less, more preferably 0.12 MPa or less, more preferably 0.10 MPa or less, more preferably 0.09 MPa or less. From the viewpoint of ensuring the ease of handling of the adhesive sheet 10 before photocuring, the shear storage modulus G1 is preferably 0.03 MPa or more, more preferably 0.04 MPa or more. Examples of methods for adjusting the shear storage modulus G1 include selecting the type of base polymer in the adhesive sheet 10, adjusting the molecular weight, and adjusting the amount of the base polymer (the same applies to the methods for adjusting the shear storage modulus G2 and the shear storage modulus G3 described below). The selection of the type of base polymer includes adjusting the composition of the monomer that forms the base polymer.

[0028] The shear storage modulus G2 is preferably 0.5 MPa or more, more preferably 0.55 MPa or more, more preferably 0.6 MPa or more, more preferably 0.65 MPa or more, more preferably 0.7 MPa or more, more preferably 0.8 MPa or more, more preferably 0.9 MPa or more, more preferably 1 MPa or more, more preferably 1.1 MPa or more, and more preferably 1.2 MPa or more, from the viewpoint of suppressing the formation of bubbles between the adherend and the pressure-sensitive adhesive sheet 10 in a state where the adherends are bonded by the pressure-sensitive adhesive sheet 10 after photocuring (from the viewpoint of suppressing bubbles). The shear storage modulus G2 is preferably 12 MPa or less, more preferably 8 MPa or less, even more preferably 5 MPa or less, and even more preferably 3.5 MPa or less, from the viewpoint of suppressing peeling from the adherend caused by the above-mentioned stress concentration in the pressure-sensitive adhesive sheet 10 bonded to the adherend.

[0029] From the viewpoint of the balance between the above-mentioned conformability to unevenness and bubble suppression, the ratio of the shear storage modulus G2 to the shear storage modulus G1 (G2 / G1) is preferably 3 or more, more preferably 5 or more, and is preferably 300 or less, more preferably 200 or less, even more preferably 100 or less, even more preferably 60 or less, and even more preferably 40 or less.

[0030] The adhesive sheet 10 has an accumulated irradiation amount of 3000 mJ / cm 2 The shear storage modulus G3 at 70°C after curing by light irradiation is preferably 0.1 MPa or more, more preferably 0.2 MPa or more, from the viewpoint of suppressing the formation of air bubbles between the adherend and the adhesive sheet 10 in a high temperature environment in a state in which the adherends are bonded by the adhesive sheet 10 after photocuring. The shear storage modulus G3 is preferably 3 MPa or less, more preferably 2.7 MPa or less, more preferably 2.4 MPa or less, more preferably 2.1 MPa or less, more preferably 1.8 MPa or less, more preferably 1.6 MPa or less, from the viewpoint of suppressing peeling from the adherend caused by the above-mentioned stress concentration in a high temperature environment in the adhesive sheet 10 bonded to the adherend. The method for measuring the shear storage modulus G3 is as described below in the examples.

[0031] The breaking strain Bs of the pressure-sensitive adhesive sheet 10 is preferably 2.0 or more, more preferably 2.5 or more, even more preferably 3.0 or more, and even more preferably 3.5 or more, from the viewpoint of ensuring stress relaxation in the pressure-sensitive adhesive sheet 10. The breaking strain Bs is preferably 30 or less, more preferably 28 or less, more preferably 26 or less, more preferably 24 or less, more preferably 22 or less, more preferably 20 or less, more preferably 18 or less, more preferably 16 or less, more preferably 14 or less, more preferably 12 or less, and more preferably 10 or less, from the viewpoint of suppressing excessive deformation of the pressure-sensitive adhesive sheet 10. In addition, the breaking strain Bs preferably satisfies Bs≦−0.17G2+6.0, from the viewpoint of suppressing excessive deformation of the pressure-sensitive adhesive sheet 10.

[0032] From the viewpoint of the balance between the above-mentioned stress relaxation properties and bubble suppression, the ratio of the breaking strain Bs to the shear storage modulus G2 (Bs / G2) is preferably 0.2 or more, more preferably 0.5 or more, more preferably 0.7 or more, more preferably 0.8 or more, more preferably 0.9 or more, more preferably 1.0 or more, more preferably 1.2 or more, more preferably 1.4 or more, more preferably 1.5 or more, more preferably 1.7 or more, more preferably 1.8 or more, more preferably 1.9 or more, and is preferably 12 or less, more preferably 10 or less, more preferably 9.0 or less, and more preferably 8.0 or less.

[0033] From the viewpoint of the above-mentioned bonding reliability, the adhesive sheet 10 preferably has an adhesive strength F of 2.0 N / 10 mm or more, more preferably 2.5 N / 10 mm or more, more preferably 3.0 N / 10 mm or more, more preferably 3.5 N / 10 mm or more, more preferably 4.0 N / 10 mm or more, more preferably 4.5 N / 10 mm or more, more preferably 5.0 N / 10 mm or more, more preferably 5.5 N / 10 mm or more, and more preferably 6.0 N / 10 mm or more in the peel test described below. The adhesive strength F is the adhesive strength to alkali glass (adhesion strength to alkali glass).

[0034] Peel test: First, a 100 mm long x 10 mm wide adhesive sheet piece of the adhesive sheet 10 is attached to an alkali glass plate produced by the float method to obtain a laminate. The adhesive sheet piece is attached to the air side (non-tin side) of the alkali glass plate. The air side is the exposed side of the alkali glass plate (the side opposite to the side in contact with the molten metal) when the alkali glass plate flows over the molten metal in the manufacturing process of the alkali glass plate. Next, the laminate is subjected to a heat and pressure treatment under conditions of 50°C, 0.5 MPa, and 15 minutes. Next, the adhesive sheet piece in the laminate is irradiated with an integrated light dose of 3000 mJ / cm from the alkali glass plate side. 2 The adhesive sheet piece is irradiated with ultraviolet light under the conditions of 23° C., a peeling angle of 180°, and a pulling speed of 300 mm / min, and one end of the adhesive sheet piece in the length direction is pulled to peel the adhesive sheet piece from the alkali glass plate, and the adhesive strength F is measured. The method for measuring the adhesive strength F is described more specifically below in the examples.

[0035] Methods for adjusting the adhesive strength F include, for example, selecting the type of base polymer in the adhesive sheet 10, adjusting the molecular weight, adjusting the degree of crosslinking, and adjusting the blending amount. Selecting the type of base polymer includes adjusting the composition of the monomers that form the base polymer. Methods for adjusting the adhesive strength F also include selecting the type of components other than the base polymer in the adhesive sheet 10, and adjusting the blending amount of the components. The components include a photopolymerizable multifunctional compound, a photopolymerization initiator, a silane coupling agent, and an oligomer.

[0036] The base polymer is preferably an acrylic polymer. The acrylic polymer is a copolymer of polymerizable components containing 50% by mass or more of an alkyl (meth)acrylate. That is, the monofunctional monomer preferably contains an alkyl (meth)acrylate. "(Meth)acrylic" means acrylic and / or methacrylic.

[0037] The (meth)acrylic acid alkyl ester is preferably a (meth)acrylic acid alkyl ester having an alkyl group having a carbon number of 1 to 20. Examples of such (meth)acrylic acid alkyl esters include methyl (meth)acrylate, ethyl (meth)acrylate, n-butyl (meth)acrylate, isobutyl (meth)acrylate, s-butyl (meth)acrylate, t-butyl (meth)acrylate, pentyl (meth)acrylate, isopentyl (meth)acrylate, neopentyl (meth)acrylate, hexyl (meth)acrylate, heptyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, isooctyl (meth)acrylate, and (meth)acrylic acid. Nonyl, isononyl (meth)acrylate, n-decyl (meth)acrylate, isodecyl (meth)acrylate, undecyl (meth)acrylate, dodecyl (meth)acrylate, n-tridecyl (meth)acrylate, isotridecyl (meth)acrylate, tetradecyl (meth)acrylate, isotetradecyl (meth)acrylate, pentadecyl (meth)acrylate, cetyl (meth)acrylate, heptadecyl (meth)acrylate, n-octadecyl (meth)acrylate, isooctadecyl (meth)acrylate, and nonadecyl (meth)acrylate. The (meth)acrylic acid alkyl ester may be used alone or in combination of two or more. The (meth)acrylic acid alkyl ester is preferably at least one selected from the group consisting of n-butyl acrylate (BA) and 2-ethylhexyl acrylate (2EHA).

[0038] The proportion of the (meth)acrylic acid alkyl ester in the monofunctional monomer is preferably 60% by mass or more, more preferably 62% by mass or more, more preferably 64% by mass or more, more preferably 65% ​​by mass or more, more preferably 67% by mass or more, more preferably 68% by mass or more, and more preferably 70% by mass or more, from the viewpoint of appropriately exhibiting basic properties such as adhesiveness in the adhesive sheet 10. This proportion is, for example, 99.9% by mass or less, 99.5% by mass or less, or 99% by mass or less.

[0039] The monofunctional monomer may include a copolymerizable monomer that is copolymerizable with the (meth)acrylic acid alkyl ester. Examples of the copolymerizable monomer include a polar group-containing monomer. Examples of the polar group-containing monomer include a hydroxy group-containing monomer, a carboxy group-containing monomer, and a monomer having a nitrogen atom-containing ring. The polar group-containing monomer is useful for modifying the acrylic polymer, such as ensuring the cohesive force of the acrylic polymer. The polar group-containing monomer is preferably at least one selected from the group consisting of a hydroxy group-containing monomer and a monomer having a nitrogen atom-containing ring.

[0040] Examples of the hydroxyl group-containing monomer include 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxybutyl (meth)acrylate, 3-hydroxypropyl (meth)acrylate, 4-hydroxybutyl (meth)acrylate, 6-hydroxyhexyl (meth)acrylate, 8-hydroxyoctyl (meth)acrylate, 10-hydroxydecyl (meth)acrylate, and 12-hydroxylauryl (meth)acrylate. The hydroxyl group-containing monomer is preferably at least one selected from the group consisting of 2-hydroxyethyl acrylate (2HEA) and 4-hydroxybutyl acrylate (4HBA).

[0041] The ratio of the hydroxy group-containing monomer in the monofunctional monomer is preferably 1% by mass or more, more preferably 2% by mass or more, more preferably 3% by mass or more, more preferably 5% by mass or more, more preferably 6% by mass or more, more preferably 7% by mass or more, and more preferably 8% by mass or more, from the viewpoint of ensuring the cohesive strength of the pressure-sensitive adhesive sheet 10. From the viewpoint of adjusting the polarity of the acrylic polymer (related to the compatibility of various additive components in the pressure-sensitive adhesive sheet 10 with the acrylic polymer), the ratio is preferably 30% by mass or less, more preferably 28% by mass or less, more preferably 26% by mass or less, more preferably 24% by mass or less, more preferably 22% by mass or less, more preferably 20% by mass or less, more preferably 18% by mass or less, more preferably 16% by mass or less, and more preferably 15% by mass or less.

[0042] Examples of carboxy group-containing monomers include acrylic acid, methacrylic acid, carboxyethyl acrylate, carboxypentyl acrylate, itaconic acid, maleic acid, fumaric acid, crotonic acid, and isocrotonic acid.

[0043] From the viewpoint of avoiding the risk of corrosion of the adherend by acid, the proportion of the carboxyl group-containing monomer in the monofunctional monomer is preferably 3 mass % or less, more preferably 1 mass % or less, even more preferably 0.5 mass % or less, and even more preferably 0.1 mass % or less.

[0044] Examples of monomers having a nitrogen atom-containing ring include N-vinyl-2-pyrrolidone, N-methylvinylpyrrolidone, N-vinylpyridine, N-vinylpiperidone, N-vinylpyrimidine, N-vinylpiperazine, N-vinylpyrazine, N-vinylpyrrole, N-vinylimidazole, N-vinyloxazole, N-(meth)acryloyl-2-pyrrolidone, N-(meth)acryloylpiperidine, N-(meth)acryloylpyrrolidine, N-vinylmorpholine, N-vinyl-3-morpholinone, N-vinyl-2-caprolactam, N-vinyl-1,3-oxazin-2-one, N-vinyl-3,5-morpholinedione, N-vinylpyrazole, N-vinylisoxazole, N-vinylthiazole, N-vinylisothiazole, and acryloylmorpholine. The monomer having a nitrogen atom-containing ring is preferably at least one selected from the group consisting of N-vinyl-2-pyrrolidone (NVP) and acryloylmorpholine (ACMO).

[0045] The proportion of the monomer having a nitrogen atom-containing ring in the monofunctional monomer is preferably 1% by mass or more, more preferably 2% by mass or more, more preferably 3% by mass or more, more preferably 5% by mass or more, more preferably 6% by mass or more, more preferably 7% by mass or more, and more preferably 8% by mass or more, from the viewpoints of ensuring the cohesive strength of the pressure-sensitive adhesive sheet 10 and ensuring the adhesive strength to the adherend in the pressure-sensitive adhesive sheet 10. The proportion is preferably 30% by mass or less, more preferably 28% by mass or less, more preferably 26% by mass or less, more preferably 24% by mass or less, more preferably 22% by mass or less, and more preferably 20% by mass or less, from the viewpoints of adjusting the glass transition temperature of the acrylic polymer and adjusting the polarity of the acrylic polymer (related to the compatibility of various additive components in the pressure-sensitive adhesive sheet with the acrylic polymer).

[0046] Examples of the photopolymerizable polyfunctional compound include polyfunctional oligomers and polyfunctional monomers.

[0047] Examples of polyfunctional oligomers include urethane acrylate oligomers (oligomers having a urethane skeleton and two or more acryloyl groups), epoxy acrylate oligomers (oligomers having an epoxy skeleton and two or more acryloyl groups), and silicone acrylate oligomers (oligomers having a siloxane skeleton and two or more acryloyl groups). Commercially available urethane acrylate oligomers include Art Resin UN-333, UN-350, UN-353, UN-5500, and UN-5590 manufactured by Negami Chemical Industries Co., Ltd.

[0048] From the viewpoint of compatibility between the monofunctional monomer and the polyfunctional oligomer, the weight average molecular weight (Mw) of the polyfunctional oligomer is preferably 5000 or more, and preferably 20000 or less, more preferably 15000 or less. The weight average molecular weight is measured by gel permeation chromatography (GPC) and calculated in terms of polystyrene.

[0049] The polyfunctional monomer may be, for example, a polyfunctional (meth)acrylate containing two or more ethylenically unsaturated double bonds in one molecule. As the polyfunctional monomer, a polyfunctional (meth)acrylate is preferable from the viewpoint of easily introducing a crosslinked structure by photopolymerization. The polyfunctional (meth)acrylate may be, for example, a bifunctional (meth)acrylate, a trifunctional (meth)acrylate, or a tetrafunctional or higher polyfunctional (meth)acrylate.

[0050] Examples of bifunctional (meth)acrylates include ethylene glycol di(meth)acrylate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol dimethacrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, glycerin di(meth)acrylate, neopentyl glycol di(meth)acrylate, stearic acid-modified pentaerythritol di(meth)acrylate, dicyclopentenyl diacrylate, and di(meth)acryloyl isocyanurate.

[0051] Examples of trifunctional (meth)acrylates include trimethylolpropane tri(meth)acrylate, pentaerythritol tri(meth)acrylate, and tris(acryloyloxyethyl)isocyanurate.

[0052] Examples of tetrafunctional or higher polyfunctional (meth)acrylates include ditrimethylolpropane tetra(meth)acrylate, pentaerythritol tetra(meth)acrylate, dipentaerythritol monohydroxypenta(meth)acrylate, alkyl-modified dipentaerythritol pentaacrylate, and dipentaerythritol hexa(meth)acrylate.

[0053] The photopolymerizable polyfunctional compound may be used alone or in combination of two or more kinds. The photopolymerizable polyfunctional compound is preferably a polyfunctional oligomer, and more preferably a urethane acrylate oligomer.

[0054] The amount of the photopolymerizable polyfunctional compound per 100 parts by mass of the monofunctional monomer is preferably 0.1 parts by mass or more, more preferably 0.3 parts by mass or more, and even more preferably 0.5 parts by mass or more, from the viewpoint of realizing good bonding reliability in the adhesive sheet 10 after photocuring that bonds between adherends. The amount of the photopolymerizable polyfunctional compound per 100 parts by mass of the monofunctional monomer is preferably 2.0 parts by mass or less, more preferably 1.8 parts by mass or less, more preferably 1.6 parts by mass or less, more preferably 1.4 parts by mass or less, more preferably 1.2 parts by mass or less, more preferably 1.0 parts by mass or less, and more preferably 0.8 parts by mass or less, from the viewpoint of ensuring softness and realizing good step conformability in the adhesive sheet 10 before photocuring.

[0055] The base polymer can be formed by photopolymerizing a polymerizable component containing a monofunctional monomer and a photopolymerizable polyfunctional compound. For example, photopolymerization by ultraviolet irradiation can be used as the photopolymerization. The polymerizable components (monofunctional monomer, photopolymerizable polyfunctional compound) may be polymerized in one step or in multiple steps. In the multistep polymerization method, first, a monofunctional monomer is polymerized (preliminary polymerization), thereby preparing a prepolymer composition containing a partial polymer (a mixture of a polymer with a low degree of polymerization and an unreacted monofunctional monomer). Next, a photopolymerizable polyfunctional compound is added to the prepolymer composition, and then a polymerization reaction is allowed to proceed in a reaction system containing the partial polymer and the photopolymerizable polyfunctional compound (main polymerization). A photopolymerization initiator is used as the polymerization initiator.

[0056] Examples of the photopolymerization initiator include a radical photopolymerization initiator, a cationic photopolymerization initiator, and an anionic photopolymerization initiator.

[0057] Examples of the radical photopolymerization initiator include an acylphosphine oxide photopolymerization initiator, a benzoin ether photopolymerization initiator, an acetophenone photopolymerization initiator, an α-ketol photopolymerization initiator, an aromatic sulfonyl chloride photopolymerization initiator, a photoactive oxime photopolymerization initiator, a benzoin photopolymerization initiator, a benzyl photopolymerization initiator, a benzophenone photopolymerization initiator, a ketal photopolymerization initiator, and a thioxanthone photopolymerization initiator.

[0058] Examples of acylphosphine oxide photopolymerization initiators include bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, bis(2,4,6-trimethylbenzoyl)-2,4-di-n-butoxyphenylphosphine oxide, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, and bis(2,6-dimethoxybenzoyl)-2,4,4-trimethylpentylphosphine oxide. Examples of benzoin ether photopolymerization initiators include benzoin methyl ether, benzoin ethyl ether, benzoin propyl ether, benzoin isopropyl ether, benzoin isobutyl ether, and 2,2-dimethoxy-2-phenylacetophenone. Examples of acetophenone photopolymerization initiators include 2,2-diethoxyacetophenone, 1-hydroxycyclohexylphenyl ketone, 4-phenoxydichloroacetophenone, and 4-(t-butyl)dichloroacetophenone. Examples of α-ketol photoinitiators include 2-methyl-2-hydroxypropiophenone and 1-[4-(2-hydroxyethyl)phenyl]-2-methylpropan-1-one. Examples of aromatic sulfonyl chloride photoinitiators include 2-naphthalenesulfonyl chloride. Examples of photoactive oxime photoinitiators include 1-phenyl-1,1-propanedione-2-(o-ethoxycarbonyl)-oxime. Examples of benzoin photoinitiators include benzoin. Examples of benzyl photoinitiators include benzil. Examples of benzophenone photoinitiators include benzophenone, benzoylbenzoic acid, 3,3'-dimethyl-4-methoxybenzophenone, and polyvinylbenzophenone. Examples of ketal photoinitiators include benzyl dimethyl ketal. Examples of the thioxanthone photopolymerization initiator include thioxanthone, 2-chlorothioxanthone, 2-methylthioxanthone, 2,4-dimethylthioxanthone, isopropylthioxanthone, 2,4-diisopropylthioxanthone, and dodecylthioxanthone. The photopolymerization initiator may be used alone or in combination of two or more kinds.The photopolymerization initiator is preferably at least one selected from the group consisting of bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, 2,2-dimethoxy-2-phenylacetophenone, and 1-hydroxycyclohexyl phenyl ketone.

[0059] The amount of photopolymerization initiator (first photopolymerization initiator) used in the preliminary polymerization (total amount of multiple photopolymerization initiators when multiple photopolymerization initiators are used) is, relative to 100 parts by mass of the monofunctional monomer, for example, 0.02 parts by mass or more, preferably 0.04 parts by mass or more, and more preferably 0.06 parts by mass or more, and for example, 1.0 part by mass or less, preferably 0.8 parts by mass or less, more preferably 0.6 parts by mass or less, more preferably 0.5 parts by mass or less, more preferably 0.4 parts by mass or less, more preferably 0.3 parts by mass or less, more preferably 0.2 parts by mass or less, and more preferably 0.1 parts by mass or less. The amount of photopolymerization initiator (second photopolymerization initiator) used in the main polymerization (total amount of multiple photopolymerization initiators when multiple photopolymerization initiators are used) is, for example, 0.1 part by mass or more, preferably 0.2 part by mass or more, and more preferably 0.3 part by mass or more, relative to 100 parts by mass of polymerizable components (monofunctional monomer, photopolymerizable polyfunctional compound), and is, for example, 2.0 parts by mass or less, preferably 1.8 parts by mass or less, more preferably 1.6 parts by mass or less, more preferably 1.4 parts by mass or less, more preferably 1.2 parts by mass or less, more preferably 1.0 part by mass or less, and more preferably 0.8 parts by mass or less.

[0060] The weight average molecular weight (Mw) of the base polymer is preferably 500,000 or more, more preferably 600,000 or more, and even more preferably 800,000 or more, from the viewpoint of ensuring the cohesive force of the pressure-sensitive adhesive sheet 10. The weight average molecular weight of the base polymer is preferably 1,200,000 or less, more preferably 1,100,000 or less, and even more preferably 1,000,000 or less, from the viewpoint of ensuring the step-following ability of the pressure-sensitive adhesive sheet 10. The weight average molecular weight of the base polymer is measured by gel permeation chromatography (GPC) and calculated in terms of polystyrene.

[0061] From the viewpoint of ensuring sufficient softness in the pressure-sensitive adhesive sheet 10 before photocuring, the glass transition temperature (Tg) of the base polymer is preferably 10°C or less, more preferably 8°C or less, more preferably 6°C or less, more preferably 4°C or less, more preferably 2°C or less, more preferably 0°C or less, more preferably -2°C or less, more preferably -4°C or less, more preferably -6°C or less, more preferably -8°C or less, more preferably -10°C or less, more preferably -12°C or less, more preferably -14°C or less, more preferably -16°C or less, more preferably -18°C or less, more preferably -20°C or less, more preferably -22°C or less, more preferably -24°C or less, more preferably -26°C or less, more preferably -28°C or less, more preferably -30°C or less, more preferably -32°C or less, more preferably -34°C or less, more preferably -36°C or less, more preferably -38°C or less, more preferably -40°C or less. The glass transition temperature is, for example, -80°C or more.

[0062] The glass transition temperature of the base polymer may be determined by the following Fox formula (theoretical value). The Fox formula is a relational expression between the glass transition temperature Tg of a polymer and the glass transition temperature Tgi of a homopolymer of a monomer constituting the polymer. In the following Fox formula, Tg represents the glass transition temperature (°C) of a polymer, Wi represents the weight fraction of a monomer i constituting the polymer, and Tgi represents the glass transition temperature (°C) of a homopolymer formed from the monomer i. The glass transition temperature of a homopolymer may be determined by a literature value. For example, the glass transition temperatures of various homopolymers are listed in "Polymer Handbook" (4th edition, John Wiley & Sons, Inc., 1999). On the other hand, the glass transition temperature of a homopolymer of a monomer may be determined by a method specifically described in JP-A-2007-51271. Fox formula: 1 / (273+Tg)=Σ[Wi / (273+Tgi)]

[0063] The polyfunctional monomer in the adhesive sheet 10 includes a polyfunctional monomer containing a cyclic structure. Examples of the polyfunctional monomer containing a cyclic structure include an alicyclic polyfunctional monomer and an aromatic ring-containing polyfunctional monomer. The cyclic structure of the alicyclic polyfunctional monomer may be a single ring, a condensed ring of a plurality of rings, or a crosslinked ring structure. That is, the alicyclic polyfunctional monomer may be a single ring alicyclic polyfunctional monomer with or without a crosslinked structure, or a condensed ring alicyclic polyfunctional monomer with or without a crosslinked structure. Examples of the cyclic structure of the alicyclic polyfunctional monomer include norbornane, tricyclodecane, tetracyclododecane, pentacyclopentadecane, adamantane, and diamantane. The cyclic structure of the aromatic ring-containing polyfunctional monomer may be a single ring, a condensed ring of a plurality of rings, or a crosslinked ring structure. That is, the aromatic ring-containing polyfunctional monomer may be a monocyclic aromatic ring-containing polyfunctional monomer with or without a crosslinked structure, or a condensed ring aromatic ring-containing polyfunctional monomer with or without a crosslinked structure. The cyclic structure-containing polyfunctional monomer may be a bifunctional monomer, or a trifunctional or higher functional monomer.

[0064] Examples of the alicyclic polyfunctional monomer include tricyclodecane dimethanol diacrylate, tricyclodecane dimethanol dimethacrylate, tris(2-acryloyloxyethyl)isocyanurate, and bis(vinylsulfone)tricyclo[5.2.1.0 2,6 ]decane. An example of an aromatic ring-containing polyfunctional monomer is ethoxylated bisphenol A diacrylate (BPAEODE). The cyclic structure-containing polyfunctional monomer is preferably an alicyclic polyfunctional monomer, more preferably an alicyclic polyfunctional monomer having a condensed ring, even more preferably an alicyclic polyfunctional monomer having a condensed ring with a crosslinked structure, and even more preferably at least one selected from the group consisting of tricyclodecane dimethanol diacrylate and tricyclodecane dimethanol dimethacrylate.

[0065] The entanglement point molecular weight Me of the homopolymer of the cyclic structure-containing polyfunctional monomer is preferably 10 or more, more preferably 20 or more, more preferably 40 or more, more preferably 60 or more, more preferably 80 or more, more preferably 100 or more, from the viewpoint of the balance between the high elasticity and stress relaxation properties of the optical adhesive sheet after photocuring. Also, preferably 400,000 or less, more preferably 380,000 or less, more preferably 360,000 or less, more preferably 340,000 or less, more preferably 320,000 or less, more preferably 300,000 or less, more preferably 270,000 or less, more preferably 250,000 or less, more preferably 230,000 or less, more preferably 200,000 or less, more preferably 170,000 or less, more preferably 150,000 or less, more preferably 130,000 or less, more preferably 100,000 or less, more preferably 80,000 or less, more preferably 60,000 or less, more preferably 50,000 or less.

[0066] The content of the cyclic structure-containing polyfunctional monomer per 100 parts by mass of the base polymer in the adhesive sheet 10 is preferably 5 parts by mass or more, more preferably 5.5 parts by mass or more, more preferably 6 parts by mass or more, more preferably 6.5 parts by mass or more, more preferably 7 parts by mass or more, more preferably 8 parts by mass or more, more preferably 9 parts by mass or more, and more preferably 10 parts by mass or more, from the viewpoint of increasing the elasticity of the adhesive sheet 10 after photocuring. The content of the cyclic structure-containing polyfunctional monomer per 100 parts by mass of the base polymer in the adhesive sheet 10 is preferably 50 parts by mass or less, more preferably 48 parts by mass or less, more preferably 46 parts by mass or less, more preferably 45 parts by mass or less, more preferably 43 parts by mass or less, more preferably 41 parts by mass or less, and more preferably 40 parts by mass or less, from the viewpoint of the stress relaxation property of the adhesive sheet 10 after photocuring.

[0067] The polyfunctional monomer may include a polyfunctional monomer that does not contain a cyclic structure (a polyfunctional monomer that does not contain a cyclic structure). Examples of such polyfunctional monomers include the polyfunctional monomers described above as the polyfunctional monomers that serve as photopolymerizable polyfunctional compounds. From the viewpoint of the stress relaxation properties of the adhesive sheet 10 after photocuring, the adhesive sheet 10 preferably does not include a polyfunctional monomer that does not contain a cyclic structure.

[0068] Examples of the photopolymerization initiator (third photopolymerization initiator) in the adhesive sheet 10 include radical photopolymerization initiators, cationic photopolymerization initiators, and anionic photopolymerization initiators, and specifically include the photopolymerization initiators described above with respect to the photopolymerization of the base polymer.

[0069] From the viewpoint of ensuring good photocurability in the adhesive sheet 10, the content of the photopolymerization initiator (third photopolymerization initiator) in the adhesive sheet 10 is, per 100 parts by mass of the base polymer, preferably 0.1 parts by mass or more, more preferably 0.15 parts by mass or more, more preferably 0.18 parts by mass or more, more preferably 0.2 parts by mass or more, more preferably 0.22 parts by mass or more, more preferably 0.24 parts by mass or more, more preferably 0.25 parts by mass or more, and also preferably 3.0 parts by mass or less, more preferably 2.8 parts by mass or less, more preferably 2.6 parts by mass or less, more preferably 2.4 parts by mass or less, more preferably 2.2 parts by mass or less, more preferably 2.0 parts by mass or less, more preferably 1.9 parts by mass or less, more preferably 1.8 parts by mass or less, more preferably 1.7 parts by mass or less, more preferably 1.6 parts by mass or less, more preferably 1.5 parts by mass or less, more preferably 1.3 parts by mass or less, and more preferably 1.0 parts by mass or less.

[0070] The pressure-sensitive adhesive sheet 10 may contain other components, such as an oligomer, an ultraviolet absorbing agent, an antioxidant, a silane coupling agent, and a rust inhibitor.

[0071] When the base polymer is an acrylic polymer, the oligomer is preferably an acrylic oligomer, which is a copolymer of polymerizable components containing 50% by mass or more of (meth)acrylic acid ester and has a weight average molecular weight of, for example, 1,000 or more and 30,000 or less.

[0072] The acrylic oligomer is preferably a polymer of a polymerizable component containing a (meth)acrylic acid alkyl ester having a chain alkyl group (chain alkyl (meth)acrylate) and a (meth)acrylic acid alkyl ester having an alicyclic alkyl group (alicyclic alkyl (meth)acrylate). Specific examples of these (meth)acrylic acid alkyl esters include the (meth)acrylic acid alkyl esters described above as the polymerizable component of the acrylic polymer.

[0073] As the chain alkyl (meth)acrylate, methyl methacrylate is preferred because it has a high glass transition temperature and excellent compatibility with the base polymer. As the alicyclic alkyl (meth)acrylate, dicyclopentanyl acrylate, dicyclopentanyl methacrylate, cyclohexyl acrylate, and cyclohexyl methacrylate are preferred. That is, the acrylic oligomer is preferably a polymer of a polymerizable component containing one or more selected from the group consisting of dicyclopentanyl acrylate, dicyclopentanyl methacrylate, cyclohexyl acrylate, and cyclohexyl methacrylate, and methyl methacrylate.

[0074] The proportion of the alicyclic alkyl (meth)acrylate in the polymerizable component of the acrylic oligomer is preferably 10% by mass or more, more preferably 12% by mass or more, more preferably 14% by mass or more, more preferably 16% by mass or more, more preferably 18% by mass or more, more preferably 20% by mass or more, more preferably 22% by mass or more, more preferably 24% by mass or more, more preferably 26% by mass or more, more preferably 28% by mass or more, more preferably 30% by mass or more. The proportion is preferably 90% by mass or less, more preferably 88% by mass or less, more preferably 86% by mass or less, more preferably 84% by mass or less, more preferably 82% by mass or less, more preferably 80% by mass or less, more preferably 78% by mass or less, more preferably 76% by mass or less, more preferably 74% by mass or less, more preferably 72% by mass or less, more preferably 70% by mass or less. The proportion of the chain alkyl (meth)acrylate in the polymerizable component of the acrylic oligomer is preferably 90% by mass or less, more preferably 88% by mass or less, more preferably 86% by mass or less, more preferably 84% by mass or less, more preferably 82% by mass or less, more preferably 80% by mass or less, more preferably 78% by mass or less, more preferably 76% by mass or less, more preferably 74% by mass or less, more preferably 72% by mass or less, more preferably 70% by mass or less. The proportion is preferably 10% by mass or more, more preferably 12% by mass or more, more preferably 14% by mass or more, more preferably 16% by mass or more, more preferably 18% by mass or more, more preferably 20% by mass or more, more preferably 22% by mass or more, more preferably 24% by mass or more, more preferably 26% by mass or more, more preferably 28% by mass or more, more preferably 30% by mass or more.

[0075] The acrylic oligomer is obtained by polymerizing the polymerizable components of the acrylic oligomer. Examples of the polymerization method include solution polymerization, bulk polymerization, and emulsion polymerization. The acrylic oligomer is preferably formed by solution polymerization. Examples of the solvent in the solution polymerization include toluene and ethyl acetate. In the polymerization of the acrylic oligomer, a thermal polymerization initiator may be used, and a chain transfer agent may be used for the purpose of adjusting the molecular weight. In this embodiment, after the formation of the acrylic oligomer, low molecular components and solvents are volatilized and removed from the reaction system such as the reaction solution by heating. Examples of the low molecular components include unreacted monomers, chain transfer agents, thermal polymerization initiators, and decomposition products (residues) thereof.

[0076] Examples of the thermal polymerization initiator include azo polymerization initiators and peroxide polymerization initiators. Examples of the azo polymerization initiator include 2,2'-azobisisobutyronitrile, 2,2'-azobis-2-methylbutyronitrile, and 2,2'-azobis(2-methylpropionate)dimethyl. Examples of the peroxide polymerization initiator include dibenzoyl peroxide, t-butyl permaleate, and lauroyl peroxide.

[0077] Chain transfer agents include α-thioglycerol, lauryl mercaptan, glycidyl mercaptan, mercaptoacetic acid, 2-mercaptoethanol, thioglycolic acid, 2-ethylhexyl thioglycolate, 2,3-dimercapto-1-propanol, and α-methylstyrene dimer.

[0078] From the viewpoint of ensuring the adhesive strength of the adhesive sheet 10, the weight average molecular weight (Mw) of the oligomer is preferably 1000 or more, more preferably 1200 or more, more preferably 1400 or more, more preferably 1500 or more, more preferably 1700 or more, more preferably 1800 or more, more preferably 2000 or more, and also preferably 30000 or less, more preferably 27000 or less, more preferably 25000 or less, more preferably 23000 or less, more preferably 20000 or less, more preferably 17000 or less, more preferably 15000 or less, more preferably 13000 or less, more preferably 10000 or less, more preferably 8000 or less. The weight average molecular weight of the oligomer is measured by gel permeation chromatography (GPC) and calculated in terms of polystyrene. The method for measuring the Mw of the oligomer is specifically as described below in relation to the examples.

[0079] The content of the oligomer in the adhesive sheet 10 is preferably 0.05 parts by mass or more, more preferably 0.07 parts by mass or more, more preferably 0.09 parts by mass or more, more preferably 0.1 parts by mass or more, more preferably 0.12 parts by mass or more, more preferably 0.14 parts by mass or more, more preferably 0.16 parts by mass or more, more preferably 0.18 parts by mass or more, and more preferably 0.2 parts by mass or more, per 100 parts by mass of the base polymer, from the viewpoint of ensuring the adhesive strength of the adhesive sheet 10. The content of the oligomer in the adhesive sheet 10 is preferably 5 parts by mass or less, more preferably 4.7 parts by mass or less, more preferably 4.5 parts by mass or less, more preferably 4.3 parts by mass or less, more preferably 4 parts by mass or less, more preferably 3.7 parts by mass or less, more preferably 3.6 parts by mass or less, and more preferably 3.5 parts by mass or less, per 100 parts by mass of the base polymer, from the viewpoint of ensuring the transparency of the adhesive sheet 10.

[0080] Examples of ultraviolet absorbents include triazine-based ultraviolet absorbents, benzotriazole-based ultraviolet absorbents, benzophenone-based ultraviolet absorbents, salicylate-based ultraviolet absorbents, and cyanoacrylate-based ultraviolet absorbents.As ultraviolet absorbents, triazine-based ultraviolet absorbents are preferred because they have high absorption of ultraviolet rays in the wavelength range of 320 nm to 370 nm and are highly compatible with acrylic polymers.The ultraviolet absorbents may be used alone or in combination of two or more kinds.

[0081] Commercially available triazine-based UV absorbers include, for example, bisethylhexyloxyphenol methoxyphenyl triazine (product name "Tinosorb S", manufactured by BASF), reaction product of 2-(4,6-bis(2,4-dimethylphenyl)-1,3,5-triazin-2-yl)-5-hydroxyphenyl with [(alkyloxy)methyl]oxirane (product name "TINUVIN 400", manufactured by BASF), reaction product of 2-(2,4-dihydroxyphenyl)-4,6-bis-(2,4-dimethylphenyl)-1,3,5-triazine with (2-ethylhexyl)-glycidic acid ester (product name "TINUVIN 405", manufactured by BASF), (2,4-bis[2-hydroxy-4-butoxyphenyl]-6-(2,4-dibutoxyphenyl)-1,3,5-triazine (product name "TINUVIN Examples of suitable phenols include 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-[(hexyl)oxy]phenol (product name "TINUVIN 577", manufactured by BASF), 2-(2-hydroxy-4-[1-octyloxycarbonylethoxy]phenyl)-4,6-bis(4-phenylphenyl)-1,3,5-triazine (product name "TINUVIN 479", manufactured by BASF), and 2-(4,6-diphenyl-1,3,5-triazin-2-yl)-5-[2-(2-ethylhexanoyloxy)ethoxy]phenol ("ADK STAB LA-46", manufactured by ADEKA).

[0082] The content of the ultraviolet absorber in the adhesive sheet 10 is preferably 0.5 parts by mass or more, more preferably 0.6 parts by mass or more, more preferably 0.7 parts by mass or more, more preferably 0.8 parts by mass or more, more preferably 0.85 parts by mass or more, more preferably 0.9 parts by mass or more, and even more preferably 1 part by mass or more, and is preferably 15 parts by mass or less, more preferably 13 parts by mass or less, more preferably 11 parts by mass or less, more preferably 10 parts by mass or less, more preferably 8 parts by mass or less, more preferably 6 parts by mass or less, more preferably 5 parts by mass or less, more preferably 4 parts by mass or less, more preferably 3 parts by mass or less, more preferably 2 parts by mass or less, more preferably 1.8 parts by mass or less, more preferably 1.6 parts by mass or less, and more preferably 1.5 parts by mass or less, per 100 parts by mass of the base polymer. Such a configuration is preferable from the viewpoint of achieving both the ultraviolet ray cutting function for device protection and the photocurability in the adhesive sheet 10.

[0083] Examples of the antioxidant include phenol-based antioxidants, phosphorus-based antioxidants, sulfur-based antioxidants, and amine-based antioxidants. The antioxidants may be used alone or in combination of two or more kinds.

[0084] As the antioxidant, a phenol-based antioxidant is preferably used, more preferably a hindered phenol-based antioxidant is used. Examples of the hindered phenol-based antioxidant include pentaerythritol tetrakis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] (product name "Irganox 1010", manufactured by BASF) and octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate (product name "Irganox 1076", manufactured by BASF).

[0085] The content of the antioxidant in the pressure-sensitive adhesive sheet 10 is preferably 0.05 parts by mass or more, more preferably 0.1 parts by mass or more, and preferably 3 parts by mass or less, more preferably 2 parts by mass or less, per 100 parts by mass of the base polymer. Such a configuration is preferable from the viewpoint of achieving both suppression of oxidative deterioration of the pressure-sensitive adhesive sheet 10 and photocurability.

[0086] Examples of the silane coupling agent include silane coupling agents containing an epoxy group. Examples of the silane coupling agent containing an epoxy group include 3-glycidoxydialkyldialkoxysilane and 3-glycidoxyalkyltrialkoxysilane. Examples of the 3-glycidoxydialkyldialkoxysilane include 3-glycidoxypropylmethyldimethoxysilane and 3-glycidoxypropylmethyldiethoxysilane. Examples of the 3-glycidoxyalkyltrialkoxysilane include 3-glycidoxypropyltrimethoxysilane and 3-glycidoxypropyltriethoxysilane. As the silane coupling agent, preferably, 3-glycidoxyalkyltrialkoxysilane is used, and more preferably, 3-glycidoxypropyltrimethoxysilane is used. The silane coupling agent may be used alone or in combination of two or more kinds. The content of the silane coupling agent in the pressure-sensitive adhesive sheet 10 is preferably 0.1 part by mass or more, more preferably 0.2 part by mass or more, and preferably 5 parts by mass or less, more preferably 3 parts by mass or less, per 100 parts by mass of the base polymer.

[0087] Examples of the rust inhibitor include benzotriazole compounds, such as 1,2,3-benzotriazole, 5-methylbenzotriazole, 4-methylbenzotriazole, and carboxybenzotriazole.

[0088] The content of the rust inhibitor in the adhesive sheet 10 is preferably 0.05 parts by mass or more, more preferably 0.1 parts by mass or more, and even more preferably 0.15 parts by mass or more, per 100 parts by mass of the base polymer, and is preferably 2 parts by mass or less, more preferably 1.7 parts by mass or less, more preferably 1.5 parts by mass or less, more preferably 1.2 parts by mass or less, more preferably 1 part by mass or less, more preferably 0.8 parts by mass or less, more preferably 0.7 parts by mass or less, more preferably 0.6 parts by mass or less, and more preferably 0.5 parts by mass or less.

[0089] The thickness of the pressure-sensitive adhesive sheet 10 is preferably 10 μm or more, more preferably 20 μm or more, and even more preferably 30 μm or more, from the viewpoint of ensuring sufficient adhesion to the adherend. The thickness of the pressure-sensitive adhesive sheet 10 is preferably 300 μm or less, more preferably 280 μm or less, more preferably 260 μm or less, more preferably 240 μm or less, more preferably 220 μm or less, more preferably 200 μm or less, more preferably 180 μm or less, more preferably 160 μm or less, more preferably 150 μm or less, more preferably 140 μm or less, more preferably 130 μm or less, more preferably 120 μm or less, and more preferably 115 μm or less, from the viewpoint of the handleability and ease of cutting of the pressure-sensitive adhesive sheet 10. In particular, when the thickness of the adhesive sheet 10 is 45 μm, 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, 85 μm, 90 μm, 95 μm, 100 μm, 105 μm, 110 μm or 115 μm, the coatability of the adhesive composition for forming the adhesive sheet 10 and the diffusibility of the later-added components within the adhesive sheet 10 are favorable, enabling stable production, which is preferable.

[0090] The light transmittance of the adhesive sheet 10 at a wavelength of 380 nm is preferably 10% or less, more preferably 9% or less, more preferably 8% or less, more preferably 7% or less, more preferably 6.5% or less, more preferably 6% or less, more preferably 5.5% or less, more preferably 5% or less, and is, for example, 0.05% or more. When the adhesive sheet 10 is used for a display panel, the adhesive sheet 10 can ensure the protection function of the display panel by blocking ultraviolet rays by having the light transmittance of the adhesive sheet 10 at a wavelength of 380 nm being equal to or less than the upper limit value. Examples of methods for adjusting the light transmittance of the adhesive sheet 10 at a wavelength of 380 nm include selecting the type of ultraviolet absorbing agent to be added to the adhesive sheet 10 and adjusting the amount.

[0091] The release liner 21 is, for example, a transparent resin film having flexibility. Examples of the material of the release liner 21 include polyester resin, polyolefin resin, polycarbonate resin, polyethersulfone resin, polyarylate resin, melamine resin, polyamide resin, cellulose resin, and polystyrene resin. Examples of the polyester resin include polyethylene terephthalate (PET), polybutylene terephthalate, and polyethylene naphthalate. Examples of the polyolefin resin include polyethylene, polypropylene, and cycloolefin polymer (COP). From the viewpoints of transparency and strength, the material of the release liner 21 is preferably a polyester resin, and more preferably PET.

[0092] The surface of release liner 21 facing adhesive sheet 10 may be release-treated with a release treatment agent. Examples of release treatments include silicone release treatments, long-chain alkyl acrylate release treatments, and fluorine release treatments. From the viewpoint of ease of adjusting the release force from adhesive sheet 10, silicone release treatments are preferred as the release treatment.

[0093] The thickness of release liner 21 is preferably 5 μm or more, more preferably 10 μm or more, and even more preferably 20 μm or more, from the viewpoint of ensuring the protective function for pressure-sensitive adhesive sheet 10. The thickness of release liner 21 is preferably 200 μm or less, more preferably 150 μm or less, and even more preferably 100 μm or less, from the viewpoint of handleability.

[0094] Release liner 22 is a flexible, transparent resin film. Examples of materials for release liner 22 include the materials described above as the materials for release liner 21. From the viewpoints of transparency and strength, the material for release liner 22 is preferably a polyester resin, and more preferably PET.

[0095] In this embodiment, the surface of the release liner 22 facing the adhesive sheet 10 is release-treated with a release treatment agent. Examples of release treatments include silicone release treatments, long-chain alkyl acrylate release treatments, and fluorine release treatments. From the viewpoint of ease of adjusting the release force from the adhesive sheet 10, silicone release treatments are preferred as the release treatment.

[0096] The thickness of release liner 22 is preferably 5 μm or more, more preferably 10 μm or more, and even more preferably 20 μm or more, from the viewpoint of ensuring the protective function for pressure-sensitive adhesive sheet 10. The thickness of release liner 22 is preferably 200 μm or less, more preferably 150 μm or less, and even more preferably 100 μm or less, from the viewpoint of handleability.

[0097] The adhesive sheet 10 can be produced, for example, as follows.

[0098] First, a prepolymer composition is prepared. Specifically, a mixture (liquid) containing the monofunctional monomer for forming the base polymer and a photopolymerization initiator (first photopolymerization initiator) is prepared (prepolymer composition preparation step). Next, the mixture is irradiated with ultraviolet light to photopolymerize a portion of the monofunctional monomer in the mixture to obtain a prepolymer composition. Examples of light sources for ultraviolet light irradiation include ultraviolet LED lights, black light lamps, high pressure mercury lamps, and metal halide lamps. In addition, in the ultraviolet light irradiation, a wavelength cut filter for cutting a portion of the wavelength range of the light emitted from the light source may be used as necessary. In the ultraviolet light irradiation, the illuminance is, for example, 5 to 200 mW / cm. 2 The cumulative irradiation dose is, for example, 100 to 5000 mJ / cm 2 The ultraviolet irradiation is preferably continued until the viscosity of the composition reaches about 15 to 25 Pa·s. This viscosity is measured using a Brookfield viscometer with a No. 5 rotor at a rotor speed of 10 rpm and at a temperature of 30°C. The prepolymer composition contains a photopolymerized product of a monofunctional monomer and a monofunctional monomer that has not undergone a polymerization reaction (residual monomer). The prepolymer composition does not contain a solvent.

[0099] Next, a photopolymerizable polyfunctional compound (crosslinking agent), a photopolymerization initiator (second photopolymerization initiator), and other components as necessary are added to the prepolymer composition to prepare a pressure-sensitive adhesive composition (pressure-sensitive adhesive composition preparation step). Examples of other components include oligomers, antioxidants, silane coupling agents, and rust inhibitors. This pressure-sensitive adhesive composition does not contain a solvent. That is, the pressure-sensitive adhesive composition prepared in this step is a solventless pressure-sensitive adhesive composition.

[0100] Next, as shown in FIG. 2A, a coating film 10A is formed between release liners 21 and 22' (coating film forming step). Specifically, first, a pressure-sensitive adhesive composition is applied onto the release surface of release liner 21 to form coating film 10A. Examples of methods for applying the pressure-sensitive adhesive composition include roll coating, kiss roll coating, gravure coating, reverse coating, roll brushing, spray coating, dip roll coating, bar coating, knife coating, air knife coating, curtain coating, lip coating, and die coating. Next, the release surface of release liner 22' is bonded onto coating film 10A on release liner 21. For example, the same release liner as release liner 22 can be used as release liner 22.

[0101] Next, as shown in Fig. 2B, ultraviolet light is irradiated onto the coating film 10A between the release liners 21 and 22' to form a base adhesive sheet 10B (base adhesive sheet forming step). During irradiation with ultraviolet light, a photopolymerization reaction proceeds in the coating film in a reaction system containing a monofunctional monomer (residual monomer) and a photopolymerizable multifunctional compound (crosslinking agent), forming a base polymer. Such a base polymer has a network structure in which linear units derived from the monofunctional monomer are linked by the photopolymerizable multifunctional compound.

[0102] Next, as shown in FIG. 2C, release liner 22' (FIG. 2B) is peeled off from base adhesive sheet 10B (peeling step).

[0103] Next, as shown in FIG. 2D, the later-added component is supplied to the base adhesive sheet 10B (later-added component supplying step). Specifically, a later-added component solution (not shown) containing the later-added component and a solvent is applied to the exposed surface of the base adhesive sheet 10B. The later-added component contains the above-mentioned cyclic structure-containing polyfunctional monomer and photopolymerization initiator (third photopolymerization initiator), and may contain other additives. Examples of the other additives include an ultraviolet absorber and an antioxidant. In this step, for example, the later-added component is allowed to penetrate into the base adhesive sheet 10B from the surface of the base adhesive sheet 10B, and the solvent is evaporated by heating as necessary. Before this step, the base polymer has already had a crosslinked structure to form the base adhesive sheet 10B. Therefore, the orange peel surface is not easily formed (not substantially formed) on the base adhesive sheet 10B by the evaporation of the solvent in this step. In addition, the photocurable adhesive sheet 10 is formed by the base adhesive sheet 10B and the later-added components. As described above, the amount of the cyclic structure-containing polyfunctional monomer added in this step is preferably 5 parts by mass or more, more preferably 5.5 parts by mass or more, more preferably 6 parts by mass or more, more preferably 6.5 parts by mass or more, more preferably 7 parts by mass or more, more preferably 8 parts by mass or more, more preferably 9 parts by mass or more, more preferably 10 parts by mass or more per 100 parts by mass of the base polymer, and is also preferably 50 parts by mass or less, more preferably 48 parts by mass or less, more preferably 46 parts by mass or less, more preferably 45 parts by mass or less, more preferably 43 parts by mass or less, more preferably 41 parts by mass or less, and more preferably 40 parts by mass or less.

[0104] Next, as shown in FIG. 2E, another release liner 22 is laminated to the pressure-sensitive adhesive sheet 10 (lamination step).

[0105] In this manner, the adhesive sheet 10 whose adhesive surface is covered and protected by the release liners 21 and 22 can be manufactured. In the above manufacturing method, the adhesive sheet 10 can be manufactured from a solvent-free adhesive composition. Such an adhesive sheet 10 does not require the solvent to be removed by volatilizing the coating film during the sheeting process, and the occurrence of orange peel-like unevenness on the surface of the adhesive sheet 10 can be suppressed. By controlling the occurrence of unevenness, good visibility can be achieved. In addition, for example, when the adhesive sheet 10 is bonded to a printed step provided on a display cover, the thicker the adhesive sheet 10 is, the easier it is to fill the printed step and the smoother the surface of the adhesive sheet 10 can be maintained (excellent step absorption), but the adhesive sheet 10 made of a solvent-free adhesive composition does not become thin due to the evaporation of the solvent during the sheeting process, so that a uniform and thick adhesive sheet 10 can be easily manufactured. And such an adhesive sheet 10 has excellent step absorption. In addition, the adhesive sheet 10 made of a solvent-free adhesive composition is suitable for reducing the environmental load. That is, the pressure-sensitive adhesive sheet 10 formed from a solvent-free pressure-sensitive adhesive composition is environmentally friendly and is preferable from the standpoint of sustainable development.

[0106] In this method, in the base adhesive sheet forming step, a base polymer having a network structure is formed from a solventless adhesive composition, and in the post-addition component supply step, a photopolymerization reaction of a multifunctional monomer (including a cyclic structure-containing multifunctional monomer) proceeds around the base polymer having a network structure. Therefore, the photopolymerization product of the multifunctional monomer is formed while forming an interpenetrating polymer network structure (IPN) with the base polymer having a network structure. This makes the optical adhesive sheet highly elastic.

[0107] On the other hand, for example, when a base polymer is formed from a solvent-based pressure-sensitive adhesive composition, a polyfunctional monomer is mixed into the solution containing the base polymer, and the polyfunctional monomer is photopolymerized, a part of the monofunctional monomer remains in the solution containing the base polymer. Therefore, the interpenetrating polymer network structure (IPN) cannot be sufficiently formed from the beginning, and the optical pressure-sensitive adhesive sheet cannot be made highly elastic. In addition, the remaining monofunctional monomer polymerizes over time, and the elasticity also changes over time.

[0108] When adhesive sheet 10 is used, release liners 21 and 22 are each peeled off from adhesive sheet 10 at a predetermined timing.

[0109] 3A to 3C show an example of a method of using the adhesive sheet 10. FIG.

[0110] In this method, first, as shown in FIG. 3A, the adhesive sheet 10 is attached to a cover glass 31 (first adherend). The cover glass 31 has a first surface 31a and a second surface 31b opposite to the first surface 31a. A decorative or light-shielding printed layer 32 is formed on the edge of the first surface 31a. The printed layer 32 is provided, for example, around the entire edge of the cover glass 31. The cover glass 31 has a step (printed step) between the first surface 31a and the surface of the printed layer 32. That is, the cover glass 31 is a stepped adherend having a step on its surface. Specifically, in this step, the adhesive sheet 10 before photocuring is attached to an area including the printed layer 32 on the surface 31a of the cover glass 31. FIG. 3A exemplarily illustrates a case in which the adhesive sheet 10 before photocuring is attached to the entire surface 31a of the cover glass 31.

[0111] 3B, the cover glass 31 and a member 33 are joined via the adhesive sheet 10 before photocuring on the cover glass 31. The member 33 is, for example, a pixel panel for a display panel, a polarizing film, or a touch panel.

[0112] Next, as shown in FIG. 3C, the adhesive sheet 10 between the member 33 and the cover glass 31 is photocured by ultraviolet irradiation. By the ultraviolet irradiation, a photopolymerization reaction of the polyfunctional monomer containing the cyclic structure-containing polyfunctional monomer proceeds in the adhesive sheet 10, and a photopolymerization product of the polyfunctional monomer is formed. Since the photopolymerization reaction proceeds around the base polymer, the photopolymerization product of the polyfunctional monomer is formed while forming an interpenetrating polymer network (IPN) with the base polymer. This makes the adhesive sheet 10 highly elastic (photocuring of the adhesive sheet 10). Examples of light sources for ultraviolet irradiation include ultraviolet LED lights, black lights, high-pressure mercury lamps, and metal halide lamps. In addition, a wavelength cut filter for cutting a part of the wavelength range of the light emitted from the light source may be used in the ultraviolet irradiation. In the ultraviolet irradiation, the illuminance is, for example, 5 to 600 mW / cm. 2 The cumulative irradiation dose is, for example, 50 to 15,000 mJ / cm 2 It is.

[0113] The adhesive sheet 10 is used, for example, as described above. In the above-mentioned method of use, the adhesive sheet 10 is used to bond two members (cover glass 31 and member 33 in the above-mentioned use example) and then photocured. Alternatively, the adhesive sheet 10 (uncured) with a release liner on one side may be attached to one member, the adhesive sheet 10 may be photocured, the release liner may be peeled off from the cured adhesive sheet 10, and then the cured adhesive sheet 10 may be used to bond the one member to the other member.

[0114] As described above, the adhesive sheet 10 includes a base polymer, a polyfunctional monomer, and a photopolymerization initiator (third photopolymerization initiator). Such an adhesive sheet 10 can be attached to a stepped surface of an adherend in a soft state before photocuring, as shown in Fig. 3A. Therefore, the adhesive sheet 10 is suitable for achieving good step-following ability when attached to an adherend having a stepped surface.

[0115] In addition, in the adhesive sheet 10, as described above, the base polymer is a photopolymerization product of a polymerizable component containing a monofunctional monomer and a photopolymerizable polyfunctional compound. Such a base polymer has a network structure in which linear units derived from a monofunctional monomer are linked by a photopolymerizable polyfunctional compound. When the adhesive sheet 10 is irradiated with light, a photopolymerization reaction of a polyfunctional monomer (including a polyfunctional monomer containing a cyclic structure) proceeds around the base polymer of such a network structure. Therefore, the photopolymerization product of the polyfunctional monomer is formed while forming an interpenetrating polymer network structure (IPN) with the base polymer of the network structure. This makes the adhesive sheet 10 highly elastic. The polyfunctional monomer containing a cyclic structure is bulkier than a polyfunctional monomer not containing a cyclic structure. Therefore, the network structure formed by the polymerization reaction of a polyfunctional monomer containing a cyclic structure-containing polyfunctional monomer has a larger mesh size than the network structure formed by the polymerization reaction of a polyfunctional monomer not containing a cyclic structure-containing polyfunctional monomer. This is suitable for achieving both high elasticity and stress relaxation properties in the adhesive sheet 10 after photocuring. Furthermore, the compatibility of high elasticity and stress relaxation properties in the photocured pressure-sensitive adhesive sheet 10 that bonds adherends together helps to achieve both the above-mentioned bubble suppression and bonding reliability.

[0116] Therefore, the pressure-sensitive adhesive sheet 10 realizes good conformability to unevenness when bonding adherends together, and is suitable for simultaneously suppressing air bubbles and ensuring bonding reliability after bonding of the adherends together. EXAMPLES

[0117] The present invention will be specifically described below with reference to examples. However, the present invention is not limited to the examples. In addition, the specific numerical values ​​of the blending amounts (contents), physical property values, parameters, etc. described below can be replaced with the upper limit (a numerical value defined as "equal to or less than") or lower limit (a numerical value defined as "equal to or more than") of the blending amounts (contents), physical property values, parameters, etc. corresponding to those described in the above-mentioned "Form for carrying out the invention".

[0118] Preparation of Acrylic Oligomer First, in a reaction vessel equipped with a stirrer, a thermometer, a reflux condenser, and a nitrogen gas inlet tube, a mixture containing 60 parts by mass of dicyclopentanyl methacrylate (DCPMA), 40 parts by mass of methyl methacrylate (MMA), 3.5 parts by mass of α-thioglycerol as a chain transfer agent, and 100 parts by mass of toluene as a polymerization solvent was stirred under a nitrogen atmosphere at 70°C for 1 hour. Next, 0.2 parts by mass of 2,2'-azobisisobutyronitrile (AIBN) as a thermal polymerization initiator was added to the mixture to prepare a reaction solution, which was reacted under a nitrogen atmosphere at 70°C for 2 hours and then at 80°C for 2 hours (polymerization reaction). Next, the reaction solution was heated at 130°C to volatilize and remove toluene, the chain transfer agent, and unreacted monomers. As a result, a solid acrylic oligomer was obtained. The weight average molecular weight of this acrylic oligomer was 5100.

[0119] Example 1 Preparation of Prepolymer Composition In a flask, 71 parts by mass of n-butyl acrylate (BA), 13 parts by mass of 4-hydroxybutyl acrylate (4HBA), 13 parts by mass of N-vinyl-2-pyrrolidone (NVP), and 3 parts by mass of acryloylmorpholine (ACMO) were added with 0.062 parts by mass of two types of first photopolymerization initiators in total, and then the mixture was irradiated with ultraviolet light under a nitrogen atmosphere to polymerize a part of the polymerizable components in the mixture to obtain a prepolymer composition. As the first photopolymerization initiator, 0.031 parts by mass of BASF's "Omnirad184" (1-hydroxycyclohexyl phenyl ketone) and 0.031 parts by mass of BASF's "Omnirad651" (2,2-dimethoxy-2-phenylacetophenone) were used. The ultraviolet light irradiation was continued until the viscosity of the composition reached about 20 Pa·s. This viscosity is a value measured using a Brookfield viscometer with a rotor No. 5 at a rotor rotation speed of 10 rpm and a temperature of 30° C. The obtained prepolymer composition is a partial polymer containing a photopolymerized product (photopolymerized polymer P1a) and a polymerizable component (residual monomer) that has not undergone a polymerization reaction.

[0120] Preparation of Pressure-Sensitive Adhesive Composition Next, 100 parts by mass of the prepolymer composition, 3 parts by mass of the acrylic oligomer, 0.6 parts by mass of a urethane acrylate oligomer (UAO) (product name "UN-350", manufactured by Negami Chemical Industries Co., Ltd.) as a photopolymerizable polyfunctional compound, 0.4 parts by mass of a second photopolymerization initiator (product name "Omnirad819", bis(2,4,6-trimethylbenzoyl)phenylphosphine oxide, manufactured by BASF), 0.5 parts by mass of an antioxidant (product name "Irganox 1010", manufactured by BASF), 0.2 parts by mass of a rust inhibitor (product name "BT-120", 1,2,3-benzotriazole, manufactured by Johoku Chemical Industry Co., Ltd.), and 0.3 parts by mass of a silane coupling agent (product name "KBM-403", manufactured by Shin-Etsu Chemical Co., Ltd.) were mixed to obtain a pressure-sensitive adhesive composition.

[0121] <Preparation of base adhesive sheet> Next, a pressure-sensitive adhesive composition was applied onto the release-treated surface of a first release liner (product name: Diafoil MRF, thickness 75 μm, manufactured by Mitsubishi Chemical Corporation) having a release-treated surface on one side to form a coating film. Next, the release-treated surface of a second release liner (product name: Diafoil MRE, thickness 75 μm, manufactured by Mitsubishi Chemical Corporation) having a release-treated surface on one side was attached onto the coating film on the first release liner. Next, the coating film between the release liners was irradiated with ultraviolet light from the second release liner side, and the coating film was photocured to form a 90 μm-thick pressure-sensitive adhesive layer (ultraviolet light irradiation step). The ultraviolet light irradiation step includes a first step and a subsequent second step. In the first step of ultraviolet light irradiation, a black light lamp (wavelength 320 nm to 400 nm, manufactured by Toshiba) was used as the light source, and the illuminance was set to 6.5 mW / cm. 2 The cumulative irradiation dose was 1500 mJ / cm 2 In the second step, ultraviolet irradiation was performed using an ultraviolet LED light (wavelength 365 nm, manufactured by Quark Technology) with an illuminance of 90 mW / cm. 2 The cumulative irradiation dose was 1800 mJ / cm 2In the ultraviolet irradiation step, a photopolymerization reaction proceeds in the coating film in a reaction system containing the above-mentioned residual monomer and photopolymerizable polyfunctional compound, forming a photopolymerized polymer P1b having a crosslinked structure. In addition, since the photopolymerization reaction proceeds around the photopolymerized polymer P1a, the photopolymerized polymer P1b is formed around the photopolymerized polymer P1a. The adhesive layer formed in this step contains such photopolymerized polymer P1a and photopolymerized polymer P1b as the base polymer P1. In this manner, a base adhesive sheet with a release liner (first release liner / base adhesive sheet (thickness 90 μm) / second release liner) was produced.

[0122] Preparation of Post-Added Component Solutions A bifunctional acrylate monomer (trade name "Light Acrylate DCP-A", tricyclodecane dimethanol diacrylate (CAS No. 42594-17-2), Kyoeisha Chemical) as a polyfunctional monomer, 27.8 parts by mass, a third photopolymerization initiator (trade name "Omnirad819", manufactured by BASF) 1.2 parts by mass, an ultraviolet absorber (trade name "Tinosorb S", manufactured by BASF) 3.6 parts by mass, and 67.4 parts by mass of ethyl acetate as a solvent were mixed to prepare a post-added component solution (everything other than the solvent in the solution is a post-added component). The composition of the post-added component solution is shown in Table 1. In Table 1, the unit of the amount of each component is the relative "parts by mass".

[0123] <Post-added component supply process> First, the second release liner was peeled off from the base adhesive sheet with the release liner, and the exposed surface of the base adhesive sheet was coated with the post-added component solution to a thickness of 30 μm. For coating, a bar coater RDS No. 14 manufactured by RDSPECIALTIES was used. Next, a drying process was performed for 3 minutes in a dryer at 110°C. By the coating process and drying process, the post-added components (multifunctional monomer, third photopolymerization initiator, ultraviolet absorber) were permeated into the base adhesive sheet, and the solvent was evaporated. A photocurable optical adhesive sheet was formed by the permeation of the post-added components into the base adhesive sheet. By the addition of the post-added components to the base adhesive sheet, the thickness of the formed optical adhesive sheet was thicker than the base adhesive sheet (the same applies to the examples and comparative examples described below). The thickness of the formed adhesive sheet is shown in Table 2. The amount of the polyfunctional monomer (DCP-A) added per 100 parts by mass of the base polymer (the total of 100 parts by mass of the above prepolymer composition and the photopolymerizable polyfunctional compound) was 8.5 parts by mass, the amount of the third photopolymerization initiator (Omnirad819) added was 0.4 parts by mass, and the amount of the ultraviolet absorber (Tinosorb S) added was 1.1 parts by mass. Next, the release-treated surface of a third release liner (product name "Diafoil MRE", thickness 75 μm, manufactured by Mitsubishi Chemical Corporation) having a release-treated surface on one side was attached to the pressure-sensitive adhesive sheet on the first release liner.

[0124] In this manner, an adhesive sheet with release liner (first release liner / adhesive sheet (thickness 103 μm) / third release liner) was produced for Example 1. The adhesive sheet was a photocurable optical adhesive sheet containing a base polymer, a multifunctional monomer (DCP-A), and a third photopolymerization initiator.

[0125] Example 2 The PSA sheet with release liner of Example 2 was produced in the same manner as the PSA sheet with release liner of Example 1, except for the following: In preparing the post-addition component solution, the composition of the post-addition component solution was changed as shown in Table 1. The thickness of the PSA sheet formed by the addition of the post-addition component was 104 μm.

[0126] Example 3 The PSA sheet with release liner of Example 3 was produced in the same manner as the PSA sheet with release liner of Example 1, except for the following: In preparing the post-addition component solution, the composition of the post-addition component solution was changed as shown in Table 1. The thickness of the PSA sheet formed by the addition of the post-addition component was 106 μm.

[0127] Example 4 The PSA sheet with release liner of Example 4 was produced in the same manner as the PSA sheet with release liner of Example 1, except for the following: In the preparation of the post-addition component solution, the composition of the post-addition component solution was changed as shown in Table 1. In the post-addition component supplying step, a bar coater RDS No. 20 manufactured by RDSPECIALTIES was used, and the coating thickness of the post-addition component solution was set to 44 μm. The thickness of the PSA sheet formed by the addition of the post-addition component was 112 μm.

[0128] Example 5 The PSA sheet with release liner of Example 5 was produced in the same manner as the PSA sheet with release liner of Example 1, except for the following: In the preparation of the post-addition component solution, the composition of the post-addition component solution was changed as shown in Table 1. In the post-addition component supplying step, a bar coater RDS No. 24 manufactured by RDSPECIALTIES was used, and the coating thickness of the post-addition component solution was set to 50 μm. The thickness of the PSA sheet formed by the addition of the post-addition component was 121 μm.

[0129] Example 6 The release-lined adhesive sheet of Example 6 was produced in the same manner as the release-lined adhesive sheet of Example 1, except for the following. In the ultraviolet irradiation step for producing the base adhesive sheet, the second step (irradiation with an ultraviolet LED light) was not performed. By such an ultraviolet irradiation step, a base polymer P2 having a weight-average molecular weight (Mw) greater than that of the base polymer P1 was formed. In the preparation of the post-addition component solution, the composition of the post-addition component solution was changed as shown in Table 1. In the post-addition component supply step, a bar coater RDS No. 10 manufactured by RDSPECIALTIES was used, and the coating thickness of the post-addition component solution was set to 23 μm. The thickness of the adhesive sheet formed by the addition of the post-addition component was 106 μm.

[0130] Example 7 The release-liner-attached PSA sheet of Example 7 was produced in the same manner as the release-liner-attached PSA sheet of Example 6, except for the following. In the preparation of the post-addition component solution, 23.8 parts by mass of a bifunctional acrylate monomer, tricyclodecane dimethanol dimethacrylate (CAS No. 43048-08-4), manufactured by Osaka Organic Chemical Industry Co., Ltd. (hereinafter sometimes referred to as DCP-DMA), was used instead of DCP-A as a polyfunctional monomer, and the composition of other components was changed as shown in Table 1. In addition, in the post-addition component supplying step, a bar coater RDS No. 16 manufactured by RDSPECIALTIES was used, and the coating thickness of the post-addition component solution was set to 37 μm. The thickness of the PSA sheet formed by the addition of the post-addition components was 103 μm.

[0131] Example 8 The PSA sheet with release liner of Example 8 was produced in the same manner as the PSA sheet with release liner of Example 7, except for the following: In preparing the post-added component solution, the composition of each component was changed as shown in Table 1. The thickness of the PSA sheet formed by the addition of the post-added components was 104 μm.

[0132] Comparative Example 1 An adhesive sheet with a release liner of Comparative Example 1 was produced in the same manner as the adhesive sheet with a release liner of Example 1, except for the following: In preparing the post-added component solution, 44.1 parts by mass of trimethylolpropane triacrylate (TMPTA) (CAS No. 15625-89-5) (product name "Viscoat #295", manufactured by Osaka Organic Chemical Industry Co., Ltd.) was blended in place of DCP-A as the multifunctional monomer, and the composition of the other components was changed as shown in Table 1. The thickness of the adhesive sheet formed by the addition of the post-added components was 106 μm.

[0133] Comparative Example 2 A release-lined adhesive sheet of Comparative Example 2 was produced in the same manner as the release-lined adhesive sheet of Example 1, except for the following: In preparing the post-addition component solution, 43.6 parts by mass of TMPTA (Viscoat #295) was blended in place of DCP-A as the polyfunctional monomer, and the composition of the other components was changed as shown in Table 1. In the post-addition component supplying step, a bar coater RDS No. 20 manufactured by RDSPECIALTIES was used, and the coating thickness of the post-addition component solution was set to 44 μm. The thickness of the adhesive sheet formed by the addition of the post-addition components was 111 μm.

[0134] Comparative Example 3 The release-lined adhesive sheet of Comparative Example 3 was produced in the same manner as the release-lined adhesive sheet of Example 1, except for the following: In preparing the post-addition component solution, 56.5 parts by mass of TMPTA (Viscoat #295) was blended in place of DCP-A as the polyfunctional monomer, and the composition of the other components was changed as shown in Table 1. In the post-addition component supplying step, a bar coater RDS No. 24 manufactured by RDSPECIALTIES was used, and the coating thickness of the post-addition component solution was set to 50 μm. The thickness of the adhesive sheet formed by the addition of the post-addition components was 122 μm.

[0135] Comparative Example 4 A release-lined PSA sheet of Comparative Example 4 (first release liner / PSA sheet / second release liner) was produced in the same manner as the release-lined PSA sheet of Example 1, except for the following: No post-added component solution was prepared, and no post-added component supplying step was carried out.

[0136] <Measurement of weight average molecular weight> The weight-average molecular weight (Mw) of the above acrylic oligomer was measured by gel permeation chromatography (GPC) under the following measurement conditions, and calculated in terms of polystyrene. A GPC measuring device (product name "HLC-8120GPC", manufactured by Tosoh Corporation) was used for the measurement. The sample solution was prepared as follows. First, a tetrahydrofuran (THF) solution (salt added) with a sample concentration of 0.15% by mass was prepared using the acrylic oligomer as a sample, and the THF solution was left to stand for 20 hours. Next, the THF solution was filtered through a membrane filter with an average pore size of 0.45 μm, and the filtrate was obtained as a sample solution for molecular weight measurement.

[0137] [GPC measurement conditions] Column: G7000H XL +GMH XL +GMH XL , TSKgel (manufactured by Tosoh) Column temperature: 40℃ Eluent: THF solution Flow rate: 0.8mL / min Sample injection volume: 100 μL Standard sample: polystyrene (Agilent) Detector: Differential refractometer (RI)

[0138] <Light transmittance> The light transmittance of each of the pressure-sensitive adhesive sheets of Examples 1 to 8 and Comparative Examples 1 to 4 was measured using a spectrophotometer (product name "U4100", manufactured by Hitachi High-Technologies). In this measurement, a sample piece (first release liner / pressure-sensitive adhesive sheet / third release liner (second release liner only in Comparative Example 4)) was cut out from the pressure-sensitive adhesive sheet, and then the sample piece was irradiated with ultraviolet light through the first release liner. For ultraviolet light irradiation, a metal halide lamp was used as the light source, and the illuminance was set to 300 mW / cm. 2 The cumulative irradiation dose was 3000 mJ / cm 2 Next, the release liners were peeled off from both sides of the pressure-sensitive adhesive sheet, and the pressure-sensitive adhesive sheet was fixed to a measurement jig of a spectrophotometer so as not to deform the pressure-sensitive adhesive sheet. In Comparative Example 4, ultraviolet irradiation was not performed. In addition, in this measurement, the temperature condition was 23°C, and the measurement wavelength range was 300 nm to 800 nm. The measured light transmittance (%) at a wavelength of 380 nm is shown in Table 2.

[0139] <Adhesive strength> For each of the pressure-sensitive adhesive sheets of Examples 1 to 8 and Comparative Examples 1 to 4, the adhesive strength was measured by the following peel test.

[0140] First, a test piece was prepared for each adhesive sheet. In preparing the test piece, first, the third release liner (only Comparative Example 4, the second release liner) was peeled off from the adhesive sheet, and a PET film (thickness 50 μm) was attached to the exposed surface of the adhesive sheet, thereby obtaining a laminated film (first release liner / adhesive sheet / PET film). Next, a test piece (length 100 mm×width 10 mm) was cut out from the laminated film. Next, in an environment of 23° C. and relative humidity 50%, the first release liner was peeled off from the adhesive sheet of the test piece, and the exposed surface of the adhesive sheet thus exposed was attached to the air side (non-tin side) of an alkali glass plate (blue plate glass, manufactured by Matsunami Glass Industry Co., Ltd.) prepared by the float method, thereby obtaining a laminate (alkali glass plate / adhesive sheet / PET film). In the lamination, the test piece was pressure-bonded to the alkali glass plate by a work of moving a 2 kg roller back and forth once. Next, the laminate was autoclaved. In the autoclave treatment, the temperature was 50°C, the pressure was 0.5 MPa, and the treatment time was 15 minutes. Next, the adhesive sheet in the laminate was irradiated with ultraviolet light from the alkali glass plate side (photocuring treatment). In the ultraviolet light irradiation, a metal halide lamp was used as the light source, and the illuminance was 300 mW / cm. 2 The cumulative irradiation dose was 3000 mJ / cm 2 Next, the laminate was left to stand for 15 hours in an environment of 23°C and 50% relative humidity. Next, a test was carried out to peel the test piece from the alkali glass plate in an environment of 23°C and 50% relative humidity to measure the peel strength. A tensile testing machine (product name "Autograph AG-Xplus 200N", manufactured by Shimadzu Corporation) was used for this measurement. In this measurement, the peel angle of the test piece against the adherend was 180°, the tensile speed of the test piece was 300 mm / min, and the peel length was 50 mm (measurement conditions for the peel test). The arithmetic mean value of the peel strength in three measurements (n=3) for each type of adhesive sheet is shown in Table 2 as the adhesive strength F (N / 10 mm) after photocuring against an alkali glass plate prepared by the float method.

[0141] Dynamic Viscoelasticity Measurement For each of the pressure-sensitive adhesive sheets of Examples 1 to 8 and Comparative Examples 1 to 4, the dynamic viscoelasticity was measured (first measurement).

[0142] First, a required number of samples for measurement were prepared for each adhesive sheet. Specifically, first, a plurality of pieces of adhesive sheet cut out from the adhesive sheet were laminated together to prepare a sample sheet having a thickness of 0.8 to 1.2 mm. Next, this sheet was punched out to obtain cylindrical pellets (diameter 8 mm) as the measurement samples.

[0143] Next, the measurement sample was subjected to dynamic viscoelasticity measurement using a dynamic viscoelasticity measuring device (name: "Advanced Rheometric Expansion System (ARES) G2", manufactured by TA Instruments). Specifically, the measurement sample was fixed to a parallel plate jig with a diameter of 8 mm of the same device, and then the measurement was performed. In this measurement, the measurement mode was shear mode, the measurement temperature was in the range of -50°C to 150°C in 5°C increments, the heating rate was 5°C / min, the frequency was 1Hz, the set load was 30g, and the set strain amount was 0.1%. Then, the shear storage modulus G1 (MPa) at 25°C was read from the measurement results. The values ​​are shown in Table 2.

[0144] Meanwhile, the dynamic viscoelasticity after photocuring was measured for each of the pressure-sensitive adhesive sheets of Examples 1 to 8 and Comparative Examples 1 to 3 (second measurement). In preparing the samples for measurement, pressure-sensitive adhesive sheets that had been photocured by irradiating the first release liner with ultraviolet light were used. For ultraviolet light irradiation, a metal halide lamp was used with an illuminance of 300 mW / cm. 2 The cumulative irradiation dose was 3000 mJ / cm 2 The load set during the measurement was 100 g. Other than these, the measuring device and the measuring conditions in the second measurement were the same as those in the first measurement described above. From the measurement results, the shear storage modulus G2 (MPa) at 25°C and the shear storage modulus G3 (MPa) at 70°C were read. The values ​​are shown in Table 2.

[0145] <Breaking strain> The amount of strain at break in a tensile breaking test was examined for each of the pressure-sensitive adhesive sheets of Examples 1 to 8 and Comparative Examples 1 to 4. Specifically, the results are as follows.

[0146] First, the adhesive sheet with release liner was irradiated with ultraviolet light through the first release liner to photocure the adhesive sheet. For ultraviolet irradiation, a metal halide lamp was used as the light source, and the illuminance was 300 mW / cm. 2 The cumulative irradiation dose was 3000 mJ / cm 2 Next, four pieces of sheets with a length of 30 mm and a width of 5 mm were cut out from the adhesive sheet with release liner. These four adhesive sheets were laminated to prepare a test piece (length 30 mm x width 5 mm). Next, the test piece was autoclaved. In the autoclaving, the temperature was 50°C, the pressure was 0.5 MPa, and the processing time was 15 minutes. Next, the test piece was pulled in the length direction until it broke (tensile test) using a tensile tester (Autograph AGS-50NX, manufactured by Shimadzu Corporation) under conditions of 25°C, initial chuck distance of 10 mm, and tensile speed of 300 mm / min. In this tensile test, the extension length ΔL of the test piece at the time when it broke was measured. The extension length ΔL is the amount of extension from the initial length of the test piece between the chucks of 10 mm (L0). The ratio (ΔL / L0) of the elongated length ΔL to the initial length of 10 mm (L0) was then calculated. The arithmetic mean value of the ratio in three tests (n=3) for each type of pressure-sensitive adhesive sheet is shown as the breaking strain Bs in Table 2. In Comparative Example 4, ultraviolet irradiation was not performed.

[0147] FIG. 4 is a graph plotting the measurement results of the shear storage modulus G2 and the breaking strain Bs of each pressure-sensitive adhesive sheet of the Examples and Comparative Examples. In the graph of FIG. 4, the horizontal axis represents the shear storage modulus G2 (MPa), and the vertical axis represents the breaking strain Bs. In FIG. 4, plots E1 to E8 represent the measurement results of Examples 1 to 8, and plots C1 to C3 represent the measurement results of Comparative Examples 1 to 3. Line L1 is a regression line based on plots C1 to C3 by the least squares method, and is a line expressed by Bs = -0.109G2 + 2.43. In contrast, line L2 is a line expressed by Bs = -0.17G2 + 3.74. Plots E1 to E8 (Examples 1 to 8) are located above line L2. That is, each pressure-sensitive adhesive sheet of Examples 1 to 8 satisfied the following formula (1). Each of the pressure-sensitive adhesive sheets of Examples 1 to 8 showed good results in the evaluation of step conformability described below, and also showed good results in the evaluation of bonding reliability described below, and also showed good results in the evaluation of foaming resistance bonding reliability described below. In other words, Examples 1 to 8, which satisfy the following formula (1), achieved good step conformability during bonding between adherends, and also achieved both bubble suppression and bonding reliability after bonding between adherends. In contrast, each of the pressure-sensitive adhesive sheets of Comparative Examples 1 to 3 showed good results in the evaluation of step conformability and foaming resistance reliability, but did not show good results in the evaluation of bonding reliability.

[0148] Bs≧-0.17G2+3.74 (1)

[0149] <Step-following ability> The step-conforming ability of each of the pressure-sensitive adhesive sheets of Examples 1 to 8 and Comparative Examples 1 to 4 was examined as follows.

[0150] First, a sample sheet (length 75 mm x width 45 mm) was cut out from the adhesive sheet with release liner. Next, the third release liner (only Comparative Example 4, second release liner) was peeled off from the adhesive sheet in the sample sheet, and the exposed surface of the adhesive sheet was bonded to the center of a PET film (length 100 mm x width 50 mm, thickness 125 μm). In bonding, a roll laminator was used, the pressure between the rolls was set to 0.2 MPa, and the feed speed was set to 100 mm / min. Next, the first release liner was peeled off from the adhesive sheet on the PET film, and the exposed surface of the adhesive sheet was bonded to a glass plate (length 100 mm x width 50 mm, thickness 500 μm) with a printed layer to obtain a bonded body (first bonded body). In bonding, a roll laminator was used, the pressure between the rolls was set to 0.2 MPa, and the feed speed was set to 100 mm / min. FIG. 5 shows the positional relationship between the glass plate 41 and the adhesive sheet 42 (optical adhesive sheet) in this first bonded body. On one surface in the thickness direction of the glass plate 41, a printed layer 43 (black ink layer) having a thickness of 45 μm is formed around the entire periphery of the edge of the glass plate 41. The printed layer 43 is formed in a range of 15 mm inward from each end of the glass plate 41 in the length direction L1, and is formed in a range of 5 mm inward from each end of the glass plate 41 in the width direction L2 (the printed layer 43 is shown hatched in FIG. 5). The adhesive sheet 42 is attached to the center of one surface in the thickness direction of the glass plate 41, and is in contact with the printed layer 43 around the entire periphery of the edge of the sheet. That is, the printed layer 43 on the glass plate 41 is sandwiched between the glass plate 41 and the adhesive sheet 42 in a range of 2.5 mm outward from the inner end of the layer.

[0151] Next, the first bonded body was autoclaved under conditions of 50°C, 0.5 MPa, and 30 minutes. After this, the vicinity of the inner edge of the printed layer 43 in the first bonded body was observed. Specifically, the inside of the inner edge of the printed layer 43 (the area where the adhesive sheet 42 should be in close contact with the glass plate 41) was observed with a digital microscope from the PET film side of the first bonded body at an observation magnification of 20. Then, with regard to the step conformability of each adhesive sheet, when no air bubbles were observed within the observed range, it was evaluated as "good", and when air bubbles were observed, it was evaluated as "poor". The results are shown in Table 2.

[0152] <Joint reliability> The adhesive reliability of each of the pressure-sensitive adhesive sheets of Examples 1 to 8 and Comparative Examples 1 to 4 was evaluated as follows.

[0153] First, an evaluation sample was prepared. In preparing the evaluation sample, a retardation layer-attached polarizing film piece (length 28 mm×width 10 mm) was cut out from the retardation layer-attached polarizing film. The retardation layer-attached polarizing film is produced as described below, and has a first surface (the surface on the retardation layer side) and a second surface (the hard coat layer surface of the TAC film described below) opposite to the first surface. Next, a sample sheet (length 25 mm x width 10 mm) was cut out from the adhesive sheet with release liner (first release liner / adhesive sheet (uncured) / third release liner (only Comparative Example 4, second release liner)). Next, the third release liner (second release liner only in Comparative Example 4) was peeled off from the adhesive sheet in the sample sheet, and the exposed surface of the adhesive sheet thus exposed was attached to the second surface of a piece of polarizing film with a retardation layer. Specifically, one end (one short side) in the length direction of the retardation layer-attached polarizing film piece was aligned with one end (one short side) in the length direction of the adhesive sheet, and the pieces were laminated together using a hand roller. Next, the first release liner was peeled off from the adhesive sheet on the retardation layer-attached polarizing film piece, and the exposed surface of the adhesive sheet was laminated to an alkali-free glass plate (product name "Eagle XG", Corning) using a hand roller. This resulted in a laminate (alkali-free glass plate / adhesive sheet / polarizing film). Next, this laminate was autoclaved for 15 minutes under conditions of 50°C and 0.5 MPa. Next, the adhesive sheet in the laminate was irradiated with ultraviolet light from the alkali-free glass plate side, and the adhesive sheet was photocured. For ultraviolet light irradiation, an LED light with a wavelength of 405 nm was used as a light source, and the illuminance was 400 mW / cm. 2 The cumulative light intensity is 3000 mJ / cm 2 In this manner, an evaluation sample (alkali-free glass plate / photocured pressure-sensitive adhesive sheet / polarizing film piece with retardation layer) was prepared.

[0154] Next, the evaluation sample was heated at 105°C for 1 hour. Next, the evaluation sample was visually observed from the alkali-free glass plate side. The adhesive sheet bonding reliability was evaluated as "good" when there was no substantial lifting or peeling between the adhesive sheet and the alkali-free glass plate and / or between the adhesive sheet and the polarizing film in the evaluation sample, and evaluated as "poor" when there was obvious lifting or peeling. The results are shown in Table 2.

[0155] As another evaluation condition, the evaluation sample was heated at 105°C for 3 hours, and then the evaluation sample was visually observed from the alkali-free glass plate side. Then, for the bonding reliability of the adhesive sheet, the evaluation sample was evaluated as "good" when there was no substantial lifting or peeling between the adhesive sheet and the alkali-free glass plate and / or between the adhesive sheet and the polarizing film, and was evaluated as "poor" when there was obvious lifting or peeling. Furthermore, after heating at 115°C for 1 hour, the evaluation sample was visually observed again from the alkali-free glass plate side. Then, for the bonding reliability of the adhesive sheet, the evaluation sample was evaluated as "excellent" when there was no substantial lifting or peeling between the adhesive sheet and the alkali-free glass plate and / or between the adhesive sheet and the polarizing film. The results are shown in Table 2. Note that in Example 7, Example 8, and Comparative Example 4, the bonding reliability after heating at 105°C for 1 hour was not evaluated, and only the bonding reliability after heating at 105°C for 3 hours and then heating at 115°C for 1 hour was evaluated.

[0156] <Preparation of polarizing film with retardation layer> As described below, a polarizing film with a pressure-sensitive adhesive layer and a retardation film were prepared, and these were bonded together (a bonding step described below) to prepare a polarizing film with a retardation layer.

[0157] <Preparation of Polarizing Film with Pressure-Sensitive Adhesive Layer> A long polyvinyl alcohol (PVA) film (product name: "PE3000", thickness: 30 μm, manufactured by Kuraray) was subjected to swelling treatment, dyeing treatment, crosslinking treatment, washing treatment, and drying treatment in this order to produce a polarizer with a thickness of 12 μm. Specifically, the process is as follows.

[0158] In the swelling treatment, the PVA film was uniaxially stretched in the longitudinal direction while immersed in a pure water bath at 20°C. A roll stretching machine was used for the uniaxial stretching (the same applies to the uniaxial stretching described below). The stretching ratio in the swelling treatment was 2.2 times.

[0159] In the dyeing treatment, the PVA film was uniaxially stretched in the longitudinal direction while immersed in a dye bath at 30°C. The dye bath was an aqueous solution containing iodine and potassium iodide in a mass ratio of 1:7. The iodine concentration in the dye bath was adjusted so that the single transmittance of the polarizer to be produced was 45.0%. The stretching ratio in the dyeing treatment was 1.4 times.

[0160] The crosslinking treatment includes a first-stage crosslinking treatment (first crosslinking treatment) and a second-stage crosslinking treatment (second crosslinking treatment). In the first crosslinking treatment, the PVA film was uniaxially stretched in the longitudinal direction while immersed in a first crosslinking bath at 40°C. The first crosslinking bath was an aqueous solution containing boric acid and potassium iodide (boric acid concentration 5.0% by mass, potassium iodide concentration 3.0% by mass). The stretching ratio in the first crosslinking treatment was 1.2 times. In the subsequent second crosslinking treatment, the PVA film was uniaxially stretched in the longitudinal direction while immersed in a second crosslinking bath at 65°C. The second crosslinking bath was an aqueous solution containing boric acid and potassium iodide (boric acid concentration 4.3% by mass, potassium iodide concentration 5.0% by mass). The stretching ratio in the second crosslinking treatment was 1.6 times.

[0161] In the washing treatment, the PVA film was immersed in an aqueous potassium iodide solution (concentration: 2.6% by mass) at 20° C. In the drying treatment, the PVA film was dried at 70° C. for 5 minutes.

[0162] In this manner, a polarizer (thickness: 12 μm) that was uniaxially stretched at a total stretch ratio of 5.9 times was produced.

[0163] Next, a first triacetyl cellulose (TAC) film (product name "KC2UA", thickness 25 μm, manufactured by Konica Minolta) was bonded to one surface of the polarizer with a polyvinyl alcohol adhesive, and a second TAC film (product name "KC2UA", thickness 25 μm, manufactured by Konica Minolta) with a hard coat layer (thickness 7 μm) was bonded to the other surface of the polarizer with a polyvinyl alcohol adhesive. The surface of the second TAC film opposite to the hard coat layer was bonded to the polarizer. This resulted in a polarizing film having a laminated structure of protective layer (with hard coat layer) / polarizer / protective layer (without hard coat).

[0164] Meanwhile, in a reaction vessel equipped with a reflux condenser, a nitrogen inlet tube, a thermometer and a stirrer, a mixture (reaction liquid) containing 79.9 parts by mass of n-butyl acrylate, 15 parts by mass of benzyl acrylate, 5 parts by mass of acrylic acid, 0.1 parts by mass of 4-hydroxybutyl acrylate (4HBA), 0.1 parts by mass of 2,2'-azoisobutyronitrile as a polymerization initiator, and ethyl acetate as a solvent was stirred under a nitrogen atmosphere at 55°C for 7 hours (polymerization reaction). Next, ethyl acetate was added to the reaction liquid to adjust the solid content concentration to 30% by mass. This resulted in a polymer solution containing an acrylic polymer. The weight average molecular weight of the acrylic polymer in the polymer solution was 2.2 million.

[0165] Next, 0.5 parts by mass of a first crosslinking agent (product name "Coronate L", trimethylolpropane / tolylene diisocyanate trimer adduct, manufactured by Tosoh Corporation), 0.1 parts by mass of a second crosslinking agent (benzoyl peroxide), 0.2 parts by mass of a silane coupling agent (product name "KBM-403", manufactured by Shin-Etsu Chemical Co., Ltd.), and 0.5 parts by mass of a polyether compound having a reactive silyl group (product name "Silyl SAT10", manufactured by Kaneka Corporation) were added to the polymer solution and mixed per 100 parts by mass of the acrylic polymer to obtain a pressure-sensitive adhesive composition.

[0166] Next, the adhesive composition was applied onto the release-treated surface of a 38 μm-thick release film (product name "MRF#38", PET film, manufactured by Mitsubishi Chemical Corporation) with one side being release-treated, to form a coating film. Next, this coating film was dried by heating at 155° C. for 1 minute. This formed an adhesive layer with a thickness of 12 μm on the release film. Next, the adhesive layer on the release film was attached to the protective layer (without hard coat) side of the above polarizing film. As a result, a polarizing film with a pressure-sensitive adhesive layer was obtained.

[0167] <Preparation of Retardation Film> First, in a reaction vessel, 26.2 parts by mass of isosorbide (ISB), 100.5 parts by mass of 9,9-[4-(2-hydroxyethoxy)phenyl]fluorene (BHEPF), 10.7 parts by mass of 1,4-cyclohexanedimethanol (1,4-CHDM), 105.1 parts by mass of diphenyl carbonate (DPC), and 0.591 parts by mass of cesium carbonate (0.2% by mass aqueous solution) as a catalyst were mixed and dissolved under a nitrogen atmosphere. At this time, the heat transfer medium temperature in the reaction vessel was set to 150°C. Next, the pressure in the reaction vessel was reduced to 13.3 kPa, and the heat transfer medium temperature was raised to 190°C in 1 hour. Phenol generated with the rise in the heat transfer medium temperature was extracted outside the reaction vessel (the same applies when the heat transfer medium temperature is raised as described below). Next, the temperature in the reaction vessel was kept at 190°C for 15 minutes, and then the pressure in the reaction vessel was changed to 6.67kPa, and the heat medium temperature was raised to 230°C in 15 minutes. After that, when the stirring torque of the stirrer equipped in the reaction vessel increased, the heat medium temperature was raised to 250°C in 8 minutes, and further, the pressure in the reaction vessel was set to 0.200kPa or less. Then, after reaching a predetermined stirring torque, the reaction was terminated, and the reaction product was extruded into water and pelletized. In this way, polycarbonate (PC) resin was obtained. The composition of this PC resin was BHEPF / ISB / 1,4-CHDM=47.4 mol% / 37.1 mol% / 15.5 mol%. In addition, the glass transition temperature of the PC resin was 136.6°C, and the reduced viscosity was 0.395 dL / g.

[0168] Next, the PC resin pellets were vacuum dried at 80°C for 5 hours, and then the pellets were used as a raw material to extrude a long resin film having a thickness of 120 μm using a film forming device. The film forming device was equipped with a single-screw extruder (screw diameter 25 mm, cylinder set temperature 220°C) manufactured by Isuzu Kakoki Co., Ltd., a T-die (width 200 mm, set temperature 220°C), a chill roll (set temperature 120°C to 130°C), and a winder. Next, the resin film was stretched in the width direction at a stretching temperature of 137°C to 139°C using a tenter stretching machine. The stretching ratio was 2.5 times. As a result, a first retardation film was obtained as a first retardation layer.

[0169] On the other hand, a liquid crystal composition was prepared by mixing 20 parts by mass of a side-chain liquid crystal polymer (weight average molecular weight 5000) represented by the following chemical formula (1) (wherein "65" and "35" are the mol % of each constituent unit), 80 parts by mass of a polymerizable liquid crystal exhibiting a nematic liquid crystal phase (trade name "Paliocolor LC242"), 5 parts by mass of a photopolymerization initiator (trade name "Irgacure 907", manufactured by Ciba Specialty Chemicals), and 200 parts by mass of cyclopentanone as a solvent. Next, the liquid crystal composition was applied to one side of a norbornene film (trade name "Zeonex", manufactured by Zeon Corporation) as a base film using a bar coater to form a coating film. Next, the coating film on the base film was dried by heating at 80°C for 4 minutes to form a liquid crystal layer (the liquid crystal in the coating film was aligned). Next, the liquid crystal layer on the substrate film was photocured by ultraviolet irradiation to form a 0.58 μm thick liquid crystal solidified layer (second retardation layer) as a second retardation film. The liquid crystal solidified layer had an in-plane retardation Re of 0 nm for light with a wavelength of 550 nm, and a retardation Rth of -71 nm in the thickness direction for light with a wavelength of 550 nm. The liquid crystal solidified layer also exhibited a refractive index characteristic of nz>nx=ny (nx=1.5326, ny=1.5326, nz=1.6550).

[0170] [ka]

[0171] One surface of the above-mentioned first retardation film (first retardation layer) and a second retardation film (second retardation layer) on a substrate film were bonded via an adhesive to prepare a retardation film with a substrate film (first retardation layer / adhesive layer / second retardation layer).

[0172] <Joining process> The first retardation layer side of the retardation film was bonded to the adhesive layer side of the above-mentioned polarizing film with adhesive layer. At this time, the polarizing film with adhesive layer and the retardation film were aligned and bonded so that the angle formed by the slow axis of the first retardation layer and the absorption axis of the polarizing film was 45 degrees counterclockwise when viewed from the first retardation layer side. In this manner, a polarizing film with a retardation layer was produced.

[0173] <Bubble-resistant reliability> For each of the pressure-sensitive adhesive sheets of Examples 1 to 8 and Comparative Examples 1 to 4, the foaming resistance reliability was evaluated.

[0174] First, a sample sheet (length 30 mm x width 30 mm) was cut out from the adhesive sheet (uncured) with a release liner. Next, the third release liner (only Comparative Example 4, the second release liner) was peeled off from the adhesive sheet in the sample sheet, and an alkali-free glass plate (Eagle XG, manufactured by Corning) was attached to the exposed surface of the adhesive sheet by using a handle roller to produce a laminate. Next, a polycarbonate plate with a hard coat (Iupilon MR58, manufactured by Mitsubishi Gas Chemical Company, thickness 1 mm) was cut out to 40 mm x 40 mm.

[0175] Next, the first release liner was peeled off from the laminate, and the polycarbonate surface of the hard-coated polycarbonate plate was attached to the exposed surface of the pressure-sensitive adhesive sheet using a handle roller. Then, the laminate was autoclaved at 50°C and 0.5 MPa for 15 minutes.

[0176] Next, the adhesive sheet in the laminate was irradiated with ultraviolet light from the non-alkali glass plate side to photocure the adhesive sheet. For ultraviolet light irradiation, an LED lamp (wavelength 405 nm) was used as the light source, and the illuminance was 400 mW / cm. 2 The cumulative irradiation dose was 3000 mJ / cm 2 In this way, an evaluation sample was manufactured.

[0177] Next, the evaluation sample was heated at 95°C for 3 hours. Next, the evaluation sample was visually observed from the alkali-free glass plate side, and the number of bubbles generated in the adhesive sheet or at the interface between the adhesive sheet and the polycarbonate plate was counted. This operation was performed twice, and the one with the larger number of bubbles was adopted. Then, regarding the bubble resistance reliability, a case in which the number of bubbles was less than 20 was evaluated as "excellent", a case in which the number of bubbles was 20 or more but less than 35 was evaluated as "good", and a case in which the number of bubbles was 35 or more was evaluated as "poor". The results are shown in Table 2.

[0178] [Table 1]

[0179] [Table 2] [Explanation of symbols]

[0180] 10 Adhesive sheet (optical adhesive sheet) H Thickness direction 21,22 Release Liner 41 Coverslip 43 Printing layer

Claims

1. An optical adhesive sheet comprising a base polymer and having photocurability, the base polymer is a photopolymer of a polymerizable component containing a monofunctional monomer and a photopolymerizable multifunctional compound, Shear storage modulus G of 0.3 MPa or less at 25°C 1 having Accumulated light intensity: 3000 mJ / cm 2 After curing by ultraviolet irradiation under the conditions of 2 However, Bs≧-0.17G 2 Optical adhesive sheet that meets +3.

74.

2. The shear storage modulus G 1 The shear storage modulus G 2 The optical adhesive sheet according to claim 1 , wherein the ratio is 300 or less.

3. The optical adhesive sheet according to claim 1 , wherein the breaking strain Bs is 2.0 or more.

4. 4. The optical adhesive sheet according to claim 1, wherein the adhesive strength F in the following peel test is 2.0 N / 10 mm or more. Peel test: First, a 100 mm long x 10 mm wide adhesive sheet piece of the optical adhesive sheet is attached to an alkali glass plate prepared by a float method to obtain a laminate. Next, the laminate is heated and pressurized at 50°C, 0.5 MPa, and 15 minutes. Next, the adhesive sheet piece in the laminate is irradiated with an integrated light quantity of 3000 mJ / cm from the alkali glass plate side. 2 The adhesive sheet piece is then irradiated with ultraviolet light under the conditions of 23° C., a peeling angle of 180°, and a pulling speed of 300 mm / min, thereby peeling the adhesive sheet piece from the alkali glass plate and measuring the adhesive strength F.

Citation Information

Patent Citations

  • Transparent pressure-sensitive adhesive sheet for flat panel display, and flat panel display

    JP2010097070A